Thermoplastic polymer particles and methods of making and using the same

The highly spherical thermoplastic polymer particles are prepared by melt emulsion method and the emulsion stabilizer is associated on their outer surface, which solves the problem of insufficient fluidity and filling efficiency of thermoplastic polymer powder particles in the prior art during 3D printing, achieving higher fluidity and lower void formation.

CN112457660BActive Publication Date: 2025-02-28XEROX CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202010815813.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-30
Filing Date
2020-08-14
Publication Date
2025-02-28
Estimated Expiration
2040-08-14

AI Technical Summary

Technical Problem

The existing thermoplastic polymer powder particles have poor powder flow performance and filling efficiency during the 3D printing process, resulting in weak structures and void formation.

Method used

Highly spherical thermoplastic polymer particles are prepared by melt emulsification method, and the emulsion stabilizer is used to associate on the outer surface of the particles to improve the fluidity of the particles.

Benefits of technology

Improves the flowability and filling efficiency of thermoplastic polymer particles, reduces the formation of voids in 3D printed items, and improves the mechanical integrity of the structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention is entitled "Thermoplastic polymer particles and methods of making and using the same". Thermoplastic polymer particles can be prepared, which include a thermoplastic polymer and an emulsion stabilizer (e.g., nanoparticles and / or surfactants) associated with the outer surface of the particles. The nanoparticles can be embedded in the outer surface of the particles. The particles can be prepared using melt emulsification. For example, the method may include: mixing a mixture including a thermoplastic polymer, a carrier fluid immiscible with the thermoplastic polymer, and an emulsion stabilizer at a temperature greater than the melting point or softening temperature of the thermoplastic polymer and at a shear rate high enough to disperse the thermoplastic polymer in the carrier fluid; cooling the mixture to below the melting point or softening temperature of the thermoplastic polymer to form thermoplastic polymer particles; and separating the thermoplastic polymer particles from the carrier fluid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to thermoplastic polymer particles and methods of making such particles. Such particles, especially highly spherical thermoplastic polymer particles, can be used, among other things, as raw materials for additive manufacturing. Background Art

[0002] Three-dimensional (3D) printing (also known as additive manufacturing) is a rapidly growing field of technology. Although 3D printing has traditionally been used for rapid prototyping activities, the technology is increasingly being used to produce commercial and industrial objects that may have structural and mechanical tolerances that are very different from those of rapid prototypes.

[0003] 3D printing operates by depositing either (a) small droplets or streams of molten or solidifiable material or (b) powder particles in precise deposition locations for subsequent consolidation into larger items, which may have any number of complex shapes. Such deposition and consolidation processes are typically performed under computer control to provide layer-by-layer buildup of larger items. In a specific example, consolidation of powder particles may be performed in a 3D printing system using a laser to facilitate selective laser sintering (SLS). Incomplete interlayer fusion may create structural weak points, which may be problematic for printing items with tight structural and mechanical tolerances.

[0004] Powder particles that can be used for 3D printing include thermoplastic polymers (including thermoplastic elastomers), metals, and other solidifiable substances. Although a wide variety of thermoplastic polymers are known, relatively few thermoplastic polymers have properties suitable for 3D printing, especially when powder bed fusion (PBF) is used. Additive manufacturing methods using powder materials include PBF, selective laser sintering (SLS), selective heat sintering (SHM), selective laser melting (SLM), electron beam melting (EBM), binder jetting, and multi-jet melting (MJF). In the SLS printing method, energy from a high-power laser fuses the particles together. Typical thermoplastic polymers suitable for 3D printing include those with a clear melting point and a recrystallization point about 20°C to 50°C lower than the melting point. This difference allows more efficient coalescence between adjacent polymer layers, thereby promoting improved structural and mechanical integrity.

[0005] In order to achieve good printing performance using powder particles (especially polymer powder particles), the powder particles need to maintain good flow characteristics in the solid state. The flow characteristics can be evaluated, for example, by measuring the fraction of powder particles in the sample that can pass through a standard sieve of a specified size and / or measuring the angle of repose. A high fraction of sievable powder particles can indicate that the particles are present in the form of non-agglomerated, essentially individual particles, which can be a feature of a ready-to-use powder flow. In contrast, a lower value of the angle of repose can be a feature of a ready-to-use powder flow. A relatively narrow particle size distribution in the sample and the regularity of the particle shape can also help promote good powder flow properties.

[0006] Commercial powder particles are typically obtained by cryogenic grinding or precipitation processes, which can produce irregular particle shapes and wide particle size distributions. Irregular particle shapes can lead to poor powder flow properties during 3D printing. In addition, powder particles with irregular shapes (especially those obtained from current commercial processes) can lead to poor filling efficiency after deposition and consolidation, thereby widely forming voids in the printed objects because the powder particles are not tightly packed together during deposition. Wide particle size distributions can similarly be problematic in this regard. Although poor powder flow properties can be addressed to a certain extent by dry mixing with fillers and flow aids, these techniques may have limited effectiveness for softer polymer materials (such as elastomers) due to particle aggregation. Summary of the invention

[0007] The present disclosure relates to thermoplastic polymer particles and methods of making such particles. Such particles, especially highly spherical thermoplastic polymer particles, can be used, among other things, as raw materials for additive manufacturing.

[0008] Described herein is a composition comprising: a particle comprising a thermoplastic polymer and an emulsion stabilizer (eg, nanoparticles and / or a surfactant) associated with an outer surface of the particle.

[0009] A method is described herein, comprising: mixing a mixture comprising a thermoplastic polymer, a carrier fluid immiscible with the thermoplastic polymer, and an emulsion stabilizer (e.g., nanoparticles and / or a surfactant) at a temperature greater than the melting point or softening temperature of the thermoplastic polymer, at a sufficiently high shear rate to disperse the thermoplastic polymer in a carrier fluid, cooling the mixture to below the melting point or softening temperature of the thermoplastic polymer to form solidified particles comprising the thermoplastic polymer and the emulsion stabilizer associated with the outer surface of the solidified particles, and separating the solidified particles from the carrier fluid. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] The following drawings are included to illustrate certain aspects of the embodiments and should not be construed as exclusive embodiments. The disclosed subject matter is capable of considerable modification, alteration, combination, and equivalents in form and function, as will occur to those skilled in the art having the benefit of this disclosure.

[0011] Figure 1 is a flow chart of a non-limiting example method 100 of the present disclosure.

[0012] Figure 2 is a scanning electron micrograph of polyamide particles.

[0013] Figure 3 is a scanning electron micrograph of polyamide particles.

[0014] Figure 4 is a scanning electron micrograph of polyamide particles.

[0015] Figure 5 is a scanning electron micrograph of polyamide particles.

[0016] Figure 6 is a scanning electron micrograph of polyamide particles.

[0017] Figure 7 is a scanning electron micrograph of polyamide particles.

[0018] Figure 8 is a scanning electron micrograph of polyamide particles.

[0019] Fig. 9 is a scanning electron micrograph of polyamide particles.

[0020] Fig.10 is a scanning electron micrograph of polyamide particles.

[0021] Fig.11 is a scanning electron micrograph of polyamide particles.

[0022] Fig.12 is a scanning electron micrograph of polyamide particles.

[0023] Fig.13 is a scanning electron micrograph of polyamide particles.

[0024] Fig.14 is a scanning electron micrograph of polyamide particles.

[0025] Fig.15 is a scanning electron micrograph of polyamide particles.

[0026] Fig.16 is a scanning electron micrograph of polyamide particles.

[0027] Fig.17is a scanning electron micrograph of polyamide particles.

[0028] Fig.18 is a scanning electron micrograph of polyamide particles.

[0029] Fig.19 is a scanning electron micrograph of polyamide particles.

[0030] Fig. 20 is a scanning electron micrograph of polyamide particles.

[0031] Fig.21 is a scanning electron micrograph of polyamide particles.

[0032] Fig. 22 is a scanning electron micrograph of polyamide particles.

[0033] FIG. 23 is a scanning electron micrograph of polyamide particles.

[0034] Fig.24 is a scanning electron micrograph of polyamide particles.

[0035] Fig.25 and Fig.26 are the volume density particle size distribution of the screened particles and the unscreened particles, respectively.

[0036] Fig. 27 An exemplary optical microscopy image of thermoplastic polyurethane microparticles at 150X magnification is shown.

[0037] Fig.28 Exemplary optical microscopy images of thermoplastic polyurethane microparticles are shown.

[0038] Fig.29A and Fig.29B Exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Comparative Example 2 at various magnifications are shown.

[0039] Fig.30 Exemplary optical microscopy images of thermoplastic polyurethane microparticles are shown.

[0040] Fig.31 An exemplary histogram of particle size of thermoplastic polyurethane microparticles is shown.

[0041] Fig.32 Exemplary optical microscopy images of thermoplastic polyurethane microparticles are shown.

[0042] Fig.33 An exemplary histogram of particle size of thermoplastic polyurethane microparticles is shown.

[0043] Fig.34 Exemplary optical microscopy images of thermoplastic polyurethane microparticles are shown.

[0044] Fig.35A and Fig.35B Exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications are shown.

[0045] Fig.36 An exemplary histogram of particle size of thermoplastic polyurethane microparticles is shown.

[0046] Fig.37 Exemplary optical microscopy images of thermoplastic polyurethane microparticles are shown.

[0047] FIG. 38A to FIG. 38D Exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications are shown.

[0048] Fig.39 An exemplary histogram of particle size of thermoplastic polyurethane microparticles is shown.

[0049] Fig.40 Exemplary optical microscopy images of thermoplastic polyurethane microparticles are shown.

[0050] FIG. 41A to FIG. 41C Exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications are shown.

[0051] Fig.42 An exemplary histogram of particle size of thermoplastic polyurethane microparticles is shown.

[0052] FIG. 43A to FIG. 43E An exemplary SEM image of TPU 90A NAT thermoplastic polyurethane microparticles (ADVANC3D) is shown.

[0053] Fig.44 Optical images of printed products obtained from thermoplastic polyurethane microparticles are shown.

[0054] Fig.45 An exemplary optical microscopy image of thermoplastic polyurethane microparticles at 150X magnification is shown.

[0055] Fig.46 An exemplary histogram of particle size of thermoplastic polyurethane microparticles is shown.

[0056] Fig.47 An exemplary optical microscopy image of thermoplastic polyurethane microparticles at 150X magnification is shown.

[0057] Fig.48A and Fig.48B Exemplary SEM images of the obtained thermoplastic polyurethane microparticles at various magnifications are shown.

[0058] Fig.49An exemplary histogram of particle size of thermoplastic polyurethane microparticles is shown.

[0059] Fig.50 An exemplary optical microscopic image of the obtained thermoplastic polyurethane microparticles at 100X magnification is shown.

[0060] Fig.51 An exemplary histogram of particle size of thermoplastic polyurethane microparticles is shown.

[0061] Fig.52 Exemplary optical microscopy images of thermoplastic polyurethane microparticles at 100X magnification are shown.

[0062] Fig.53 An exemplary histogram of particle size of thermoplastic polyurethane microparticles is shown.

[0063] Fig.54 An exemplary optical microscopy image of thermoplastic polyurethane microparticles at 300X magnification is shown.

[0064] Fig.55 An exemplary histogram of particle size of thermoplastic polyurethane microparticles is shown.

[0065] Fig.56 An exemplary optical microscopy image of thermoplastic polyurethane microparticles at 150X magnification is shown.

[0066] Fig.57 An exemplary histogram of particle size of thermoplastic polyurethane microparticles is shown.

[0067] Fig.58 An exemplary optical microscopy image of thermoplastic polyurethane microparticles at 150X magnification is shown.

[0068] Fig.59 An exemplary histogram of particle size of thermoplastic polyurethane microparticles is shown.

[0069] Fig.60 An exemplary optical microscopy image of thermoplastic polyurethane microparticles at 150X magnification is shown.

[0070] Fig.61A and Fig.61B Exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications are shown.

[0071] Fig.62 An exemplary histogram of particle size of thermoplastic polyurethane microparticles is shown.

[0072] Fig.63 An exemplary optical microscopy image of thermoplastic polyurethane microparticles at 150X magnification is shown.

[0073] Fig.64 An exemplary histogram of particle size of thermoplastic polyurethane microparticles is shown.

[0074] Fig.65 An exemplary particle size distribution graph of thermoplastic polyurethane microparticles is shown.

[0075] Fig.66 An optical image of the printed product is shown. DETAILED DESCRIPTION

[0076] The present disclosure relates to thermoplastic polymer particles and methods of making such particles. Such particles, especially highly spherical thermoplastic polymer particles, can be used, among other things, as raw materials for additive manufacturing.

[0077] More specifically, the thermoplastic polymer particles described herein are prepared by a melt emulsification method, wherein the thermoplastic polymer is dispersed in a carrier fluid that is immiscible with the thermoplastic polymer in the form of a melt. A sufficient amount of shear is used to form droplets in the carrier fluid from the thermoplastic polymer melt. An emulsion stabilizer (e.g., nanoparticles and / or surfactants, including one or more members of each type in some cases) causes surface tension at the phase interface between the carrier fluid and the thermoplastic polymer melt. Once the melt emulsification process is complete, the dispersion is cooled so that the polymer solidifies into thermoplastic polymer particles.

[0078] Without being limited by theory, during the melt emulsification process, the emulsion stabilizer is mainly located at the interface between the polymer melt and the carrier fluid. Therefore, when the mixture is cooled, the emulsion stabilizer remains at the interface. Advantageously, the emulsion stabilizer at the surface of the resulting particles can contribute to the flow characteristics of the resulting particles.

[0079] As previously described, conventional methods of forming thermoplastic polymer particles having good flowability include at least two steps, which include first forming (e.g., by cryogenic grinding or precipitation processes) and purifying the particles, and secondly coating the particles to some extent with a flow enhancer such as nanoparticle silica, carbon black, or PTFE particles. The methods described herein advantageously prepare thermoplastic polymer particles having a coating that enhances the flowability of the particles in one process.

[0080] In addition, without being limited by theory, the method of the present disclosure appears to produce particles with more uniform coverage of the emulsion stabilizer, which can further improve flowability. Enhanced flowability is particularly beneficial for additive manufacturing applications, such as 3D printing.

[0081] Definition and test methods

[0082] As used herein, the term "immiscible" refers to a mixture of components that, when combined, form two or more phases that have less than 5 weight % solubility in each other at ambient pressure and room temperature or the melting points of the components if they are solid at room temperature. For example, polyethylene oxide having a molecular weight of 10,000 g / mol is solid at room temperature and has a melting point of 65° C. Thus, if a material that is liquid at room temperature and the polyethylene oxide have less than 5 weight % solubility in each other at 65° C., the polyethylene oxide is immiscible with the material.

[0083] As used herein, the term "thermoplastic polymer" refers to a plastic polymer material that can reversibly soften and harden when heated and cooled. Thermoplastic polymers encompass thermoplastic elastomers.

[0084] As used herein, the term "elastomer" refers to a copolymer comprising a crystalline "hard" segment and an amorphous "soft" segment. For example, in the case of a polyurethane, the crystalline segment may include a portion of a polyurethane having carbamate functional groups and optional chain extender groups, and the soft segment may include a polyol.

[0085] As used herein, the term "polyurethane" refers to the polymer reaction product between a diisocyanate, a polyol, and an optional chain extender.

[0086] As used herein, the term "oxide" refers to both metal oxides and non-metal oxides. For the purposes of this disclosure, silicon is considered a metal.

[0087] As used herein, the terms "associated," "associated," and grammatical variations thereof between an emulsion stabilizer and a surface refer to chemical bonding and / or physical adhesion of the emulsion stabilizer to the surface. Without being limited by theory, it is believed that the association between the polymers described herein and the emulsion stabilizer is primarily physical adhesion via hydrogen bonding and / or other mechanisms. However, chemical bonding may occur to some extent.

[0088] As used herein, the term "embedded" with respect to nanoparticles and polymer particle surfaces means that the nanoparticles extend at least partially into the surface such that the polymer contacts the nanoparticles to a greater extent than would be achieved if the nanoparticles were simply laid on the polymer particle surface.

[0089] As used herein, D10, D50, D90 and diameter span are primarily used herein to describe particle size. As used herein, the term "D10" refers to the diameter at which 10% of the sample (on a volume basis unless otherwise specified) consists of particles with a diameter less than the stated diameter value. As used herein, the term "D50" refers to the diameter at which 50% of the sample (on a volume basis unless otherwise specified) consists of particles with a diameter less than the stated diameter value. As used herein, the term "D90" refers to the diameter at which 90% of the sample (on a volume basis unless otherwise specified) consists of particles with a diameter less than the stated diameter value.

[0090] As used herein, the terms "diameter span" and "span" and "span size" when referring to diameter provide an indication of the breadth of the particle size distribution and are calculated as (D90-D10) / D50 (again unless otherwise indicated, each D value is based on volume).

[0091] By using the Malvern MASTERSIZER TM Particle size was determined by light scattering techniques or analysis of optical digital micrographs of the ATmega 3000. Unless otherwise specified, light scattering techniques were used to analyze particle size.

[0092] For light scattering techniques, the control sample is the product of the trade name Quality Audit Standards QAS4002 TM Glass microspheres with diameters ranging from 15 μm to 150 μm were purchased from Malvern Analytical Ltd. Samples were analyzed as dry powders unless otherwise indicated. TM The particles to be analyzed were dispersed in air and analyzed using the 3000. The particle size was derived from a plot of bulk density versus size using the instrument software.

[0093] Particle size measurements and diameter spans can also be determined by optical digital microscopy.Optical images were obtained using a Keyence VHX-2000 digital microscope and version 2.3.5.1 software for particle size analysis (system version 1.93).

[0094] As used herein, when referring to sieving, the hole / sieve size is described in terms of United States Standard Sieve (ASTM E11-17).

[0095] As used herein, the terms "roundness" and "sphericity" with respect to particles refer to how close a particle is to a perfect sphere. To determine roundness, an optical microscopic image is taken of the particle. The perimeter (P) and area (A) of the particle in the plane of the microscopic image are calculated (e.g., using a SYSMEX FPIA 3000 particle shape and size analyzer, available from Malvern Instruments). The roundness of a particle is C EA / P, where C EA It is the circumference of a circle whose area is equal to the area (A) of the actual particle.

[0096] As used herein, the term "sintering window" refers to the difference between the melting temperature (Tm) onset and the crystallization temperature (Tc) onset or (Tm-Tc) onset. Tm, Tm (onset), Tc, and Tc (onset) are determined by differential scanning calorimetry at a ramp rate of 10 ° C / min and a cooling rate of 10 ° C / min according to ASTM E794-06 (2018).

[0097] As used herein, the term "shear" refers to stirring or similar processes that cause mechanical agitation in a fluid.

[0098] As used herein, the term "aspect ratio" refers to the length divided by the width, wherein the length is greater than the width.

[0099] Unless otherwise indicated, the melting point of the polymers was determined by ASTM E794-06 (2018) with a 10°C / min ramp rate and cooling rate.

[0100] Unless otherwise indicated, the softening temperature or softening point of a polymer is determined by ASTM D6090-17.The softening temperature can be measured using a cup and ball apparatus commercially available from Mettler-Toledo using a 0.50 gram sample at a heating rate of 1°C / min.

[0101] The angle of repose is a measure of the flowability of a powder. Angle of repose measurements were determined using ASTM D6393-14 "Standard Test Method for Bulk Solids Characterized by Carr Indices" using a Hosokawa Micron Powder Characterization Tester PT-R.

[0102] Hausner ratio (Hausner ratio, H r ) is a measure of the flowability of the powder and is given by H r =ρ 振实 / ρ 堆积Calculate, where ρ 堆积 is the bulk density according to ASTM D6393-14, and ρ 振实 It is the tap density according to ASTM D6393-14.

[0103] As used herein, the term "embedded" with respect to nanoparticles and polymer particle surfaces means that the nanoparticles extend at least partially into the surface such that the polymer contacts the nanoparticles to a greater extent than would be achieved if the nanoparticles were simply laid on the polymer particle surface.

[0104] As used herein, unless otherwise specified, the viscosity of the carrier fluid is the kinematic viscosity at 25° C., measured in accordance with ASTM D445-19. For commercially available carrier fluids (e.g., PDMS oil), the kinematic viscosity data cited herein are provided by the manufacturer, whether measured in accordance with the aforementioned ASTM or another standard measurement technique.

[0105] Thermoplastic polymer particles and preparation method

[0106] Figure 1 1 is a flow chart of a non-limiting example method 100 of the present disclosure. At 108, a thermoplastic polymer 102, a carrier fluid 104, and an emulsion stabilizer 106 are combined to produce a mixture 110. The components 102, 104, and 106 may be added in any order and include mixing and / or heating during the process of combining the components 102, 104, and 106 at 108.

[0107] The mixture 110 is then processed at 112 by applying sufficiently high shear to the mixture 110 at a temperature greater than the melting point or softening temperature of the thermoplastic polymer 102 to form a molten emulsion 114. Since the temperature is above the melting point or softening temperature of the thermoplastic polymer 102, the thermoplastic polymer 102 becomes a polymer melt. The shear rate should be high enough to disperse the polymer melt in the carrier fluid 104 in the form of droplets (i.e., polymer emulsion 114). Without being limited by theory, it is believed that increasing shear should reduce the size of the droplets of polymer melt in the carrier fluid 104, all other factors being equal. However, at some point there may be diminishing returns to increasing shear and reducing droplet size, and / or there may be damage to the contents of the droplets, thereby reducing the quality of the particles produced therefrom.

[0108] The molten emulsion 114 inside and / or outside the mixing vessel is then cooled at 116 to solidify the polymer droplets into thermoplastic polymer particles (also referred to as solidified thermoplastic polymer particles). The cooled mixture 118 may then be processed at 120 to separate the thermoplastic polymer particles 122 from other components 124 (e.g., carrier fluid 104, excess emulsion stabilizer 106, etc.), and to wash or otherwise purify the thermoplastic polymer particles 122. The thermoplastic polymer particles 122 include the thermoplastic polymer 102 and at least a portion of the emulsion stabilizer 106 coating the outer surface of the thermoplastic polymer particles 122. The emulsion stabilizer 106 or a portion thereof may be deposited on the thermoplastic polymer particles 122 as a uniform coating. In some cases, which may depend on non-limiting factors such as temperature (including cooling rate), type of thermoplastic polymer 102, and type and size of emulsion stabilizer 106, nanoparticles of emulsion stabilizer 106 may be at least partially embedded within the outer surface of thermoplastic polymer particles 122 during association with the outer surface of the thermoplastic polymer particles 122. Even if embedding does not occur, at least the nanoparticles within the emulsion stabilizer 106 may remain robustly associated with the thermoplastic polymer particles 122 to facilitate further use thereof. In contrast, dry blending already formed thermoplastic polymer microparticles (e.g., formed by cryogenic grinding or precipitation processes) with a flow aid (such as silica nanoparticles) does not produce a robust, uniform coating of the flow aid on the thermoplastic polymer microparticles.

[0109] Advantageously, the carrier fluid and wash solvent of the systems and methods described herein (eg, method 101) can be recycled and reused. One skilled in the art will recognize any necessary cleaning of the spent carrier fluid and solvent required during the recycling process.

[0110] The thermoplastic polymer 102 and the carrier fluid 104 should be selected so that they are immiscible at various processing temperatures (e.g., from room temperature to the processing temperature). An additional factor that may be considered is the difference (e.g., difference or ratio) in viscosity between the molten polyamide 102 and the carrier fluid 104 at the processing temperature. The viscosity difference may affect droplet breakup and particle size distribution. Without being limited by theory, it is believed that when the viscosities of the molten polyamide 102 and the carrier fluid 104 are too similar, the roundness of the product as a whole may be reduced, with the particles being more oval and more elongated structures observed.

[0111] Examples of thermoplastic polymers 102 include, but are not limited to, polyamides, polyurethanes, polyethylenes, polypropylenes, polyacetals, polycarbonates, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyesters (e.g., polylactic acid), polyethers, polyethersulfones, polyetheretherketones, polyacrylates, polymethacrylates, polyimides, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymers, polyarylene ethers, polyarylene sulfide, polysulfones, polyetherketones, polyamide-imides, polyetherimides, polyetheresters, copolymers comprising polyether blocks and polyamide blocks (PEBA or polyether block amides), grafted or non-grafted thermoplastic polyolefins. , functionalized or non-functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / (meth) acrylate alkyl esters, functionalized or non-functionalized (meth) acrylic polymers, functionalized or non-functionalized ethylene / vinyl monomer / (meth) acrylate alkyl ester terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / (meth) acrylate alkyl ester / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicones, and the like, and any combination thereof. Copolymers comprising one or more of the foregoing substances may also be used in the methods and systems of the present disclosure.

[0112] The thermoplastic polymer 102 in the compositions and methods of the present disclosure can be elastomeric or non-elastomeric. Some of the foregoing examples of thermoplastic polymers 102 can be elastomeric or non-elastomeric, depending on the exact composition of the polymer. For example, polyethylene, which is a copolymer of ethylene and propylene, can be elastomeric and independent of the amount of propylene in the polymer.

[0113] Thermoplastic elastomers generally belong to one of six categories: styrenic block copolymers, thermoplastic polyolefin elastomers, thermoplastic vulcanizates (also called elastomer alloys), thermoplastic polyurethanes, thermoplastic copolyesters, and thermoplastic polyamides (generally block copolymers containing polyamides). Examples of thermoplastic elastomers can be found in the following literature: Handbook of Thermoplastic Elastomers, 2nd edition, edited by BMW Walker and CP Rader, Van Nostrand Reinhold, New York, 1988. Examples of thermoplastic elastomers include, but are not limited to, elastomeric polyamides, polyurethanes, copolymers containing polyether blocks and polyamide blocks (PEBA or polyether block amides), methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, polybutadiene, polyisoprene, styrenic block copolymers and polyacrylonitrile, silicones, and the like. The elastic styrenic block copolymer may include at least one block selected from the group consisting of isoprene, isobutylene, butene, ethylene / butylene, ethylene-propylene, and ethylene-ethylene / propylene. More specific examples of elastic styrenic block copolymers include, but are not limited to, poly(styrene-ethylene / butylene), poly(styrene-ethylene / butylene-styrene), poly(styrene-ethylene / propylene), poly(styrene-ethylene / propylene-styrene), poly(styrene-ethylene / propylene-styrene-ethylene-propylene), poly(styrene-butadiene-styrene), poly(styrene-butylene-butadiene-styrene), and the like, and any combination thereof.

[0114] Examples of polyamides include, but are not limited to, polycaprolactam (nylon 6, polyamide 6, or PA6), poly(hexamethylene succinamide) (nylon 4,6, polyamide 4,6, or PA4,6), polyhexamethylene adipamide (nylon 6,6, polyamide 6,6, or PA6,6), polypentamethylene adipamide (nylon 5,6, polyamide 5,6, or PA5,6), polyhexamethylene sebacamide (nylon 6,10, polyamide 6,10, or PA6,10), polyundecanamide (nylon 11, polyamide 11, or PA11), polydodecaneamide (nylon 12, polyamide 12, or PA12), and polyhexamethylene terephthalamide (nylon 6T, polyamide 6 T or PA6T), nylon 10,10 (polyamide 10,10 or PA10,10), nylon 10,12 (polyamide 10,12 or PA10,12), nylon 10,14 (polyamide 10,14 or PA10,14), nylon 10,18 (polyamide 10,18 or PA10,18), nylon 6,18 (polyamide 6,18 or PA6,18), nylon 6,12 (polyamide 6,12 or PA6,12), nylon 6,14 (polyamide 6,14 or PA6,14), nylon 12,12 (polyamide 12,12 or PA12,12), etc. and any combination thereof. Copolyamides can also be used. Examples of copolyamides include, but are not limited to, PA 11 / 10,10, PA 6 / 11, PA 6,6 / 6, PA 11 / 12, PA 10,10 / 10,12, PA 10,10 / 10,14, PA 11 / 10,36, PA 11 / 6,36, PA 10,10 / 10,36, PA 6T / 6,6, etc. and any combination thereof. A polyamide followed by a first number of commas and a second number of main chain carbons is a polyamide having a first number of main chain carbons between nitrogens for segments without pendant =O groups and a second number of main chain carbons between two nitrogens for segments with pendant =O groups. As a non-limiting example, nylon 6,10 is [NH-(CH2)6-NH-CO-(CH2)8-CO] n A polyamide followed by a quantitative backslash number is a copolymer of the polyamide indicated by the numbers before and after the backslash.

[0115] Examples of polyurethanes include, but are not limited to, polyether polyurethanes, polyester polyurethanes, mixed polyether and polyester polyurethanes, and the like, and any combination thereof. Examples of thermoplastic polyurethanes include, but are not limited to, poly[4,4'-methylenebis(phenyl isocyanate)-alternative-1,4-butanediol / di(propylene glycol) / polycaprolactone], 1190A (a polyether polyurethane elastomer available from BASF), 1190A10 (a polyether polyurethane elastomer available from BASF), etc. and any combination thereof.

[0116] Compatibilizers may optionally be used to improve the blending efficiency and effectiveness of the thermoplastic polyester with one or more thermoplastic polymers. Examples of polymer compatibilizers include, but are not limited to, PROPOLDER TM MPP2020 20 (polypropylene, available from Polygroup Inc.), PROPOLDER TM MPP2040 40 (polypropylene, available from Polygroup Inc.), NOVACOM TM HFS2100 (maleic anhydride functionalized high density polyethylene polymer, available from Polygroup Inc.), KEN-REACT TM CAPS TM L TM 12 / L (organic metal coupling agent, available from Kenrich Petrochemicals), KEN-REACT TM CAPOW TM L TM 12 / H (organic metal coupling agent, available from Kenrich Petrochemicals), KEN-REACT TM LICA TM 12 (organic metal coupling agent, available from Kenrich Petrochemicals), KEN-REACT TM CAPS TM KPR TM 12 / LV (organic metal coupling agent, available from Kenrich Petrochemicals), KEN-REACT TM CAPOW TM KPR TM 12 / H (organic metal coupling agent, available from Kenrich Petrochemicals), KEN-REACT TM Titanates and zirconates (organometallic coupling agents available from Kenrich Petrochemicals), VISTAMAXX TM (ethylene-propylene copolymer, available from ExxonMobil), SANTOPRENE TM (a thermoplastic vulcanizate of EPDM and polypropylene, available from ExxonMobil), VISTALONTM (EPDM rubber, available from ExxonMobil), EXACT TM (plastomer, available from ExxonMobil), EXXELOR TM (polymer resin, available from ExxonMobil), FUSABOND TM M603 (random ethylene copolymer, available from DOW), FUSABOND TM E226 (anhydride-modified polyethylene, available from Dow Chemical Company (DOW)), BYNEL TM 41E710 (co-extrudable adhesive resin, available from DOW), SURLYN TM 1650 (ionomer resin, available from DOW), FUSABOND TM P353 (a chemically modified polypropylene copolymer available from DOW), ELVALOY TM PTW (ethylene terpolymer, available from DOW), ELVALOY TM 3427AC (copolymer of ethylene and butyl acrylate, available from DOW Chemical Company (DOW)), LOTADER TM AX8840 (ethylene-acrylate based terpolymer, available from Arkema), LOTADER TM 3210 (ethylene-acrylate based terpolymer, available from Arkema), LOTADER TM 3410 (ethylene-acrylate based terpolymer, available from Arkema), LOTADER TM 3430 (ethylene-acrylate based terpolymer, available from Arkema), LOTADER TM 4700 (ethylene-acrylate based terpolymer, available from Arkema), LOTADER TM AX8900 (ethylene-acrylate based terpolymer, available from Arkema), LOTADER TM 4720 (ethylene-acrylate based terpolymer, available from Arkema), BAXXODUR TM EC 301 (amine of epoxy resin, available from BASF), BAXXODUR TMEC 311 (amine of epoxy resin, available from BASF), BAXXODUR TM EC 303 (amine of epoxy resin, available from BASF), BAXXODUR TM EC 280 (amine of epoxy resin, available from BASF), BAXXODUR TM EC 201 (amine of epoxy resin, available from BASF), BAXXODUR TM EC 130 (amine of epoxy resin, available from BASF), BAXXODUR TM EC 110 (amine of epoxy resin, available from BASF), styrene, polypropylene, polyamide, polycarbonate, EASTMAN TM G-3003 (a maleic anhydride grafted polypropylene available from Eastman), RETAIN TM (polymer modifier, available from DOW Chemical Company (DOW)), AMPLIFY TY TM (maleic anhydride grafted polymer, available from DOW Chemical Company (DOW)), INTUNE TM (olefin block copolymer, available from The Dow Chemical Company (DOW)), etc. and any combination thereof.

[0117] Thermoplastic polymer 102 may have a melting point or softening temperature of about 50°C to about 450°C (or about 50°C to about 125°C, or about 100°C to about 175°C, or about 150°C to about 280°C, or about 200°C to about 350°C, or about 300°C to about 450°C).

[0118] The thermoplastic polymer 102 may have a glass transition temperature (derived from ASTM E1356-08 (2014) using a 10°C / min ramp rate and cooling rate) of about -50°C to about 400°C (or about -50°C to about 0°C, or about -25°C to about 50°C, or about 0°C to about 150°C, or about 100°C to about 250°C, or about 150°C to about 300°C, or about 200°C to about 400°C).

[0119] The thermoplastic polymer 102 may optionally include an additive. Typically, the additive will be present before the thermoplastic polymer 102 is added to the mixture 110. Thus, the additive is dispersed throughout the thermoplastic polymer in the thermoplastic polymer melt droplets and the resulting thermoplastic polymer particles. Thus, for clarity, the additive is referred to herein as an "internal additive." The internal additive may be blended with the thermoplastic polymer just prior to preparing the mixture 110 or well in advance.

[0120] When describing the amounts of components in the compositions described herein (e.g., the mixture 110 and the thermoplastic polymer particles 122), internal additives are not accounted for based on the weight percentage of the thermoplastic polymer 102. For example, a composition comprising 1 wt% emulsion stabilizer is a composition comprising 0.9 g of emulsion stabilizer, 90 g of thermoplastic polymer, and 10 g of internal additive, based on the weight of 100 g of thermoplastic polymer 102 comprising 10 wt% of internal additive and 90 wt% of thermoplastic polymer.

[0121] The internal additive may be present in the thermoplastic polymer 102 at about 0.1 wt % to about 60 wt % (or about 0.1 wt % to about 5 wt %, or about 1 wt % to about 10 wt %, or about 5 wt % to about 20 wt %, or about 10 wt % to about 30 wt %, or about 25 wt % to about 50 wt %, or about 40 wt % to about 60 wt %) of the thermoplastic polymer 102. For example, the thermoplastic polymer 102 may include about 70 wt % to about 85 wt % of the thermoplastic polymer and about 15 wt % to about 30 wt % of the internal additive, such as glass fiber or carbon fiber.

[0122] Examples of internal additives include, but are not limited to, fillers, reinforcing agents, pigments, pH adjusters, and the like, and combinations thereof. Examples of fillers include, but are not limited to, glass fibers, glass particles, mineral fibers, carbon fibers, oxide particles (e.g., titanium dioxide and zirconium dioxide), metal particles (e.g., aluminum powder), and the like, and any combination thereof. Examples of pigments include, but are not limited to, organic pigments, inorganic pigments, carbon black, and the like, and any combination thereof.

[0123] Thermoplastic polymer 102 may be present in mixture 110 at about 5 wt % to about 60 wt % (or about 5 wt % to about 25 wt %, or about 10 wt % to about 30 wt %, or about 20 wt % to about 45 wt %, or about 25 wt % to about 50 wt %, or about 40 wt % to about 60 wt %) of the combined thermoplastic polymer 102 and carrier fluid 104.

[0124] Suitable carrier fluids 104 have a viscosity of about 1,000 cSt to about 150,000 cSt (or about 1,000 cSt to about 60,000 cSt, or about 40,000 cSt to about 100,000 cSt, or about 75,000 cSt to about 150,000 cSt) at 25°C.

[0125] Examples of the carrier fluid 104 include, but are not limited to, silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, polyethylene glycol with an alkyl terminal (e.g., a C1-C4 terminal alkyl group such as tetraethylene glycol dimethyl ether (TDG)), paraffin, liquid petrolatum, vison oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, calophyllum oil, palm oil, parleam oil, grape seed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, almond oil, castor oil, avocado oil, jojoba oil, olive oil, corn germ oil, esters of lanolic acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty acid esters, higher fatty acids, fatty alcohols, polysiloxanes modified with fatty acids, polysiloxanes modified with fatty alcohols, polysiloxanes modified with polyoxyalkylenes, and the like, and any combination thereof. Examples of silicone oils include, but are not limited to, polydimethylsiloxane, methylphenylpolysiloxane, alkyl-modified polydimethylsiloxane, alkyl-modified methylphenylpolysiloxane, amino-modified polydimethylsiloxane, amino-modified methylphenylpolysiloxane, fluorine-modified polydimethylsiloxane, fluorine-modified methylphenylpolysiloxane, polyether-modified polydimethylsiloxane, polyether-modified methylphenylpolysiloxane, and the like, and any combination thereof. The carrier fluid 104 may have one or more phases. For example, a polysiloxane modified with a fatty acid and a polysiloxane modified with a fatty alcohol (preferably the fatty acid and the fatty alcohol have similar chain lengths) may form a single-phase carrier fluid 104. In another example, a carrier fluid 104 comprising a silicone oil and a polyethylene glycol terminated with an alkyl group may form a two-phase carrier fluid 104.

[0126] The carrier fluid 104 may be present in the mixture 110 at about 40 wt % to about 95 wt % (or about 75 wt % to about 95 wt %, or about 70 wt % to about 90 wt %, or about 55 wt % to about 80 wt %, or about 50 wt % to about 75 wt %, or about 40 wt % to about 60 wt %) of the combined thermoplastic polymer 102 and the carrier fluid 104.

[0127] In some cases, carrier fluid 104 may have a relative humidity of about 0.6 g / cm 3 To about 1.5g / cm 3 The thermoplastic polymer 102 has a density of about 0.7 g / cm 3 To about 1.7g / cm 3 wherein the thermoplastic polymer has a similar, lower or higher density than the density of the carrier fluid.

[0128] Emulsion stabilizers used in the methods and compositions of the present disclosure may include nanoparticles (eg, oxide nanoparticles, carbon black, polymer nanoparticles, and combinations thereof), surfactants, and the like, and any combination thereof.

[0129] Oxide nanoparticles can be metal oxide nanoparticles, non-metal oxide nanoparticles or their mixtures. Examples of oxide nanoparticles include, but are not limited to, silicon dioxide, titanium dioxide, zirconium oxide, aluminum oxide, iron oxide, copper oxide, tin oxide, boron oxide, cerium oxide, thallium oxide, tungsten oxide, etc. and any combination thereof. Mixed metal oxides and / or non-metal oxides such as aluminosilicates, borosilicates and aluminoborosilicates are also included in the term metal oxide. Oxide nanoparticles can be hydrophilic or hydrophobic, which may be natural to the particles or the result of surface treatment of the particles. For example, silicon dioxide nanoparticles with hydrophobic surface treatment (such as dimethylsilyl, trimethylsilyl, etc.) can be used in the methods and compositions of the present invention. In addition, silicon dioxide with functional surface treatment (such as methacrylate functionality) can be used in the methods and compositions of the present invention. Non-functionalized oxide nanoparticles may also be suitable for use.

[0130] Commercially available examples of silica nanoparticles include, but are not limited to, those available from Evonik Particles (e.g. R812S (with hydrophobic modified surface and 260±30m 2 / g BET surface area of ​​about 7nm average diameter silica nanoparticles), RX50 (with hydrophobic modified surface and 35±10m 2 / g BET surface area of ​​about 40nm average diameter silica nanoparticles), 380 (with hydrophilic modified surface and 380±30m 2 / g of BET surface area of ​​silica nanoparticles)) and the like and any combination thereof.

[0131] Carbon black is another type of nanoparticle that can be present as an emulsion stabilizer in the compositions and methods disclosed herein. Various grades of carbon black are familiar to those of ordinary skill in the art, and any of these grades of carbon black can be used herein. Other nanoparticles that can absorb infrared radiation can similarly be used.

[0132] Polymer nanoparticles are another type of nanoparticles that can be present in the form of emulsion stabilizers in the present disclosure. Suitable polymer nanoparticles can include one or more polymers that are thermosetting and / or crosslinked so that they do not melt when processed by melt emulsification according to the present disclosure. High molecular weight thermoplastic polymers with high melting points or decomposition points can similarly include suitable polymer nanoparticle emulsion stabilizers.

[0133] The nanoparticles can have an average diameter (D50 based on volume) of about 1 nm to about 500 nm (or about 10 nm to about 150 nm, or about 25 nm to about 100 nm, or about 100 nm to about 250 nm, or about 250 nm to about 500 nm).

[0134] Nanoparticles can have a size of about 10 m 2 / g to about 500m 2 / g(or about 10m 2 / g to about 150m 2 / g, or about 25m 2 / g to about 100m 2 / g, or about 100m 2 / g to about 250m 2 / g, or about 250m 2 / g to about 500m 2 / g) of BET surface area.

[0135] The nanoparticles can be included in the mixture 110 at a concentration of about 0.01 wt % to about 10 wt % (or about 0.01 wt % to about 1 wt %, or about 0.1 wt % to about 3 wt %, or about 1 wt % to about 5 wt %, or about 5 wt % to about 10 wt %) based on the weight of the thermoplastic polymer 102.

[0136] The surfactant may be anionic, cationic, nonionic or zwitterionic. Examples of surfactants include, but are not limited to, sodium lauryl sulfate, sorbitan oleate, poly[dimethylsiloxane-co-[3-(2-(2-hydroxyethoxy)ethoxy)propylmethylsiloxane], sodium docusate (sodium 1,4-bis(2-ethylhexyloxy)-1,4-dioxobutane-2-sulfonate), and the like, and any combination thereof. Commercially available examples of surfactants include, but are not limited to, DB-45 (sodium dodecyl diphenyl ether disulfonate, available from Pilot Chemicals), 80 (Sorbitan maleate nonionic surfactant), Surfactants (available from Stepan Company), TERGITOL TM TMN-6 (a water-soluble, nonionic surfactant available from DOW), TRITON TM X-100 (octylphenol ethoxylate, available from Sigma Aldrich), CA-520 (polyoxyethylene (5) isooctylphenyl ether, available from Sigma Aldrich), S10 (polyethylene glycol octadecyl ether, available from Sigma Aldrich), etc. and any combination thereof.

[0137] The surfactant may be included in the mixture 110 at a concentration of about 0.01 wt % to about 10 wt % (or about 0.01 wt % to about 1 wt %, or about 0.5 wt % to about 2 wt %, or about 1 wt % to about 3 wt %, or about 2 wt % to about 5 wt %, or about 5 wt % to about 10 wt %) based on the weight of the polyamide 102. Alternatively, the mixture 110 may not include (or be absent) a surfactant.

[0138] The weight ratio of nanoparticles to surfactant may be from about 1:10 to about 10:1 (or from about 1:10 to about 1:1, or from about 1:5 to about 5:1, or from about 1:1 to about 10:1).

[0139] As described above, the components 102, 104, and 106 may be added in any order and include mixing and / or heating during the process of combining the components 102, 104, and 106 at 108. For example, the emulsion stabilizer 106 may be dispersed in the carrier fluid 104 prior to adding the thermoplastic polymer 102, and the dispersion may be optionally heated. In another non-limiting example, the thermoplastic polymer 102 may be heated to produce a polymer melt, to which the carrier fluid 104 and the emulsion stabilizer 106 are added together or in any order. In yet another non-limiting example, the thermoplastic polymer 102 and the carrier fluid 104 may be mixed at a temperature greater than the melting point or softening temperature of the thermoplastic polymer 102, and at a sufficient shear rate to disperse the thermoplastic polymer melt in the carrier fluid 104. The emulsion stabilizer 106 may then be added to form a mixture 110 and maintained under suitable processing conditions for a set period of time.

[0140] The components 102, 104, and 106 may be combined at 108 in any combination in a mixing device and / or another suitable container for processing 112. As a non-limiting example, the thermoplastic polymer 102 may be heated to a temperature greater than the melting point or softening temperature of the thermoplastic polymer 102 in a mixing device for processing 112, and the emulsion stabilizer 106 may be dispersed in the carrier fluid 104 in another container. The dispersion may then be added to the melt of the thermoplastic polymer 102 in the mixing device for processing 112.

[0141] The mixing apparatus used for processing 112 to produce molten emulsion 114 should be capable of maintaining molten emulsion 114 at a temperature greater than the melting point or softening temperature of thermoplastic polymer 102 and applying sufficient shear rate to disperse the polymer melt in the carrier fluid 104 in the form of droplets.

[0142] Examples of mixing devices for use in processing 112 to produce molten emulsion 114 include, but are not limited to, extruders (e.g., continuous extruders, batch extruders, etc.), stirred reactors, mixers, reactors with in-line homogenizer systems, and the like, and devices derived therefrom.

[0143] The molten emulsion 114 is processed 112 and formed under suitable processing conditions (eg, temperature, shear rate, etc.) for a set period of time.

[0144] The temperature of processing 112 and forming molten emulsion 114 should be a temperature greater than the melting point or softening temperature of thermoplastic polymer 102 and less than the decomposition temperature of any component 102, 104, and 106 in mixture 110. For example, the temperature of processing 112 and forming molten emulsion 114 can be about 1°C to about 50°C (or about 1°C to about 25°C, or about 5°C to about 30°C, or about 20°C to about 50°C) greater than the melting point or softening temperature of thermoplastic polymer 102, provided that the temperature of processing 112 and forming molten emulsion 114 is less than the decomposition temperature of any component 102, 104, and 106 in mixture 110.

[0145] The shear rate of processing 112 and forming molten emulsion 114 should be high enough to disperse the polymer melt in the form of droplets in carrier fluid 104. The droplets should include droplets having a diameter of about 1000 μm or less (or about 1 μm to about 1000 μm, or about 1 μm to about 50 μm, or about 10 μm to about 100 μm, or about 10 μm to about 250 μm, or about 50 μm to about 500 μm, or about 250 μm to about 750 μm, or about 500 μm to about 1000 μm).

[0146] The time for maintaining the temperature and shear rate for processing 112 and forming molten emulsion 114 can be from 10 seconds to 18 hours or longer (or 10 seconds to 30 minutes, or 5 minutes to 1 hour, or 15 minutes to 2 hours, or 1 hour to 6 hours, or 3 hours to 18 hours). Without being limited by theory, it is believed that a steady state of droplet size will be reached, at which time processing 112 can be stopped. This time can also depend on the temperature, shear rate, thermoplastic polymer 102 composition, carrier fluid 104 composition, and emulsion stabilizer 106 composition, among other things.

[0147] The molten emulsion 114 may then be cooled at 116. Cooling 116 may range from slow (e.g., allowing the molten emulsion to cool under ambient conditions) to fast (e.g., quenching). For example, the cooling rate may range from about 10°C / hour to about 100°C / second to almost instantaneous when quenching (e.g., in dry ice) (or about 10°C / hour to about 60°C / hour, or about 0.5°C / minute to about 20°C / minute, or about 1°C / minute to about 5°C / minute, or about 10°C / minute to about 60°C / minute, or about 0.5°C / second to about 10°C / second, or about 10°C / second to about 100°C / second).

[0148] During cooling, little or no shear may be applied to the molten emulsion 114. In some cases, the shear applied during heating may also be applied during cooling.

[0149] The cooled mixture 118 resulting from cooling 116 the molten emulsion 114 comprises solidified thermoplastic polymer particles 122 (or simply thermoplastic polymer particles) and other components 124 (e.g., carrier fluid 104, excess emulsion stabilizer 106, etc.). The thermoplastic polymer particles may be dispersed in the carrier fluid or settled in the carrier fluid.

[0150] The cooled mixture 118 may then be processed at 120 to separate the thermoplastic polymer particles 122 (or simply thermoplastic polymer particles 122) from other components 124. Suitable processing includes, but is not limited to, washing, filtering, centrifuging, decanting, and the like, and any combination thereof.

[0151] The solvent used to wash the thermoplastic polymer particles 122 should generally be (a) miscible with the carrier fluid 104 and (b) non-reactive with (e.g., non-swelling and non-dissolving) the thermoplastic polymer 102. The choice of solvent will depend on, among other things, the composition of the carrier fluid and the composition of the thermoplastic polymer 102.

[0152] Examples of solvents include, but are not limited to, hydrocarbon solvents (e.g., pentane, hexane, heptane, octane, cyclohexane, cyclopentane, decane, dodecane, tridecane and tetradecane), aromatic hydrocarbon solvents (e.g., benzene, toluene, xylene, 2-methylnaphthalene and cresol), ether solvents (e.g., diethyl ether, tetrahydrofuran, diisopropyl ether and dioxane), ketone solvents (e.g., acetone and methyl ethyl ketone), alcohol solvents (e.g., methanol, ethanol, isopropanol and n-propanol), ester solvents (e.g., ethyl acetate, methyl acetate, butyl acetate, butyl propionate and butyl butyrate), halogenated solvents (e.g., chloroform, bromoform, 1,2-dichloromethane, 1,2-dichloroethane, carbon tetrachloride, chlorobenzene and hexafluoroisopropanol), water, the like and any combination thereof.

[0153] The solvent may be removed from the thermoplastic polymer particles 122 by drying using an appropriate method such as air drying, heat drying, reduced pressure drying, freeze drying, or a mixture thereof. Heating may preferably be performed at a temperature below the glass transition point of the thermoplastic polymer (e.g., about 50°C to about 150°C).

[0154] The thermoplastic polymer particles 122 separated from the other components 124 may optionally be further classified to prepare purified thermoplastic polymer particles 128. For example, in order to narrow the particle size distribution (or reduce the diameter span), the thermoplastic polymer particles 122 may be passed through a sieve having a pore size of about 10 μm to about 250 μm (or about 10 μm to about 100 μm, or about 50 μm to about 200 μm, or about 150 μm to about 250 μm).

[0155] In another exemplary purification technique, the thermoplastic polymer particles 122 may be washed with water to remove the surfactant while retaining substantially all of the nanoparticles associated with the surface of the thermoplastic polymer particles 122. In yet another exemplary purification technique, the thermoplastic polymer particles 122 may be blended with additives to achieve a desired final product. For clarity, such additives are referred to herein as "external additives" because they are blended with the thermoplastic particles 122 or other particles obtained by the methods described herein after the particles have solidified. Examples of external additives include glidants, other polymer particles, fillers, and the like, and any combination thereof.

[0156] In some cases, the surfactant used to prepare the thermoplastic polymer particles 122 may be undesirable in downstream applications. Thus, yet another exemplary purification technique may include at least substantially removing the surfactant from the thermoplastic polymer particles 122 (eg, by washing and / or pyrolysis).

[0157] Thermoplastic polymer particles 122 and / or purified thermoplastic polymer particles 128 (referred to as particles 122 / 128 ) can be characterized by composition, physical structure, and the like.

[0158] As described above, the emulsion stabilizer is at the interface between the polymer melt and the carrier fluid. Thus, when the mixture is cooled, the emulsion stabilizer remains at or near the interface. Thus, the structure of the particles 122 / 128 typically includes an emulsion stabilizer that is (a) dispersed on the outer surface of the particles 122 / 128 and / or (b) embedded in the exterior of the particles 122 / 128 (e.g., the exterior 1 volume %).

[0159] In addition, in the case where voids are formed inside the polymer melt droplets, the emulsion stabilizer 106 should generally be at the interface between the interior of the void and the thermoplastic polymer (and / or embedded in the interface). The void generally does not contain a thermoplastic polymer. Instead, the void may contain, for example, a carrier fluid, air, or be empty. The particles 122 / 128 may contain a carrier fluid at about 5% by weight or less (or about 0.001% by weight to about 5% by weight, or about 0.001% by weight to about 0.1% by weight, or about 0.01% by weight to about 0.5% by weight, or about 0.1% by weight to about 2% by weight, or about 1% by weight to about 5% by weight) of the particles 122 / 128.

[0160] Thermoplastic polymer 102 may be present in particle 122 / 128 at about 90% to about 99.5% by weight (or about 90% to about 95% by weight, or about 92% to about 97% by weight, or about 95% to about 99.5% by weight) of particle 122 / 128.

[0161] The emulsion stabilizer 106 may be present in the particles 122 / 128 at about 10% or less by weight (or about 0.01% to about 10% by weight, or about 0.01% to about 1% by weight, or about 0.5% to about 5% by weight, or about 3% to about 7% by weight, or about 5% to about 10% by weight) of the particles 122 / 128. When purified to at least substantially remove a surfactant or another emulsion stabilizer, the emulsion stabilizer 106 may be present in the particles 128 at less than 0.01% by weight (or 0% to about 0.01% by weight, or 0% to 0.001% by weight).

[0162] After forming thermoplastic microparticles according to the disclosure herein, at least a portion of nanoparticles (such as silica nanoparticles) can be disposed on the outer surface of the thermoplastic microparticles in the form of a coating. At least a portion of the surfactant (if used) can also be associated with the outer surface. The coating can be substantially uniformly disposed on the outer surface. As used herein with respect to the coating, the term "substantially uniform" refers to a uniform coating thickness in the surface position (particularly the entire outer surface) covered by the coating composition (e.g., nanoparticles and / or surfactant). The emulsion stabilizer 106 can form a coating covering at least 5% (or about 5% to about 100%, or about 5% to about 25%, or about 20% to about 50%, or about 40% to about 70%, or about 50% to about 80%, or about 60% to about 90%, or about 70% to about 100%) of the surface area of ​​the particles 122 / 128. When purified to at least substantially remove a surfactant or another emulsion stabilizer, the emulsion stabilizer 106 may be present in the particle 128 at less than 25% (or 0% to about 25%, or about 0.1% to about 5%, or about 0.1% to about 1%, or about 1% to about 5%, or about 1% to about 10%, or about 5% to about 15%, or about 10% to about 25%) of the surface area of ​​the particle 128. Image analysis of SEM micrographs may be used to determine the coverage of the emulsion stabilizer 106 on the outer surface of the particle 122 / 128. The emulsion stabilizer 106 may form a coating covering at least 5% (or about 5% to about 100%, or about 5% to about 25%, or about 20% to about 50%, or about 40% to about 70%, or about 50% to about 80%, or about 60% to about 90%, or about 70% to about 100%) of the surface area of ​​the particle 122 / 128. When purified to at least substantially remove a surfactant or another emulsion stabilizer, the emulsion stabilizer 106 may be present in the particles 128 at less than 25% (or 0% to about 25%, or about 0.1% to about 5%, or about 0.1% to about 1%, or about 1% to about 5%, or about 1% to about 10%, or about 5% to about 15%, or about 10% to about 25%) of the surface area of ​​the particles 128. Image analysis of SEM micrographs may be used to determine the coverage of the emulsion stabilizer 106 on the exterior surface of the particles 122 / 128.

[0163] The particles 122 / 128 may have a D10 of about 0.1 μm to about 125 μm (or about 0.1 μm to about 5 μm, about 1 μm to about 10 μm, about 5 μm to about 30 μm, or about 1 μm to about 25 μm, or about 25 μm to about 75 μm, or about 50 μm to about 85 μm, or about 75 μm to about 125 μm), a D50 of about 0.5 μm to about 200 μm (or about 0.5 μm to about 10 μm, or about 5 μm to about 50 μm, or about 30 μm to about 100 μm, or about 30 μm to about 70 μm, or about 25 μm to about 50 μm, or about 50 μm to about 100 μm, or about 75 μm to about 150 μm, or about 100 μm to about 200 μm), and a D90 of about 3 μm to about 300 μm (or about 3 μm to about 15 μm, or about 10 μm to about 50 μm, or about 25 μm to about 75 μm, or about 70 μm to about 200 μm, or about 60 μm to about 150 μm, or about 150 μm to about 300 μm), where D10 < D50 < D90. The particles 122 / 128 may also have a diameter span of about 0.2 to about 10 (or about 0.2 to about 0.5, or about 0.4 to about 0.8, or about 0.5 to about 1.0, or about 1 to about 3, or about 2 to about 5, or about 5 to about 10). Without limitation, a diameter span value of 1.0 or greater is considered wide, and a diameter span value of 0.75 or less is considered narrow. Without limitation, a diameter span value of 1.0 or greater is considered wide, and a diameter span value of 0.75 or less is considered narrow.

[0164] In a first non - limiting example, the particles 122 / 128 may have a D10 of about 0.1 μm to about 10 μm, a D50 of about 0.5 μm to about 25 μm, and a D90 of about 3 μm to about 50 μm, where D10 < D50 < D90. The particles 122 / 128 may have a diameter span of about 0.2 to about 2.

[0165] In a second non - limiting example, the particles 122 / 128 may have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm, and a D90 of about 70 μm to about 120 μm, where D10 < D50 < D90. The particles 122 / 128 may have a diameter span of about 1.0 to about 2.5.

[0166] In a third non - limiting example, the particles 122 / 128 may have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm, and a D90 of about 110 μm to about 175 μm, where D10 < D50 < D90. The particles 122 / 128 may have a diameter span of about 0.6 to about 1.5.

[0167] In a fourth non-limiting example, the particles 122 / 128 may have a D10 of from about 75 μm to about 125 μm, a D50 of from about 100 μm to about 200 μm, and a D90 of from about 125 μm to about 300 μm, where D10 < D50 < D90. The particles 122 / 128 may have a diameter span of from about 0.2 to about 1.2.

[0168] In a fifth non-limiting example, the particles 122 / 128 may have a D10 of from about 1 μm to about 50 μm (or from about 5 μm to about 30 μm, or from about 1 μm to about 25 μm, or from about 25 μm to about 50 μm), a D50 of from about 25 μm to about 100 μm (or from about 30 μm to about 100 μm, or from about 30 μm to about 70 μm, or from about 25 μm to about 50 μm, or from about 50 μm to about 100 μm), and a D90 of from about 60 μm to about 300 μm (or from about 70 μm to about 200 μm, or from about 60 μm to about 150 μm, or from about 150 μm to about 300 μm), where D10 < D50 < D90. The particles 122 / 128 may also have a diameter span of from about 0.4 to about 3 (or from about 0.6 to about 2, or from about 0.4 to about 1.5, or from about 1 to about 3).

[0169] The particles 122 / 128 may have a roundness of about 0.7 or greater (or from about 0.7 to about 0.95, or from about 0.9 to about 1.0, or from about 0.93 to about 0.99, or from about 0.95 to about 0.99, or from about 0.97 to about 0.99, or from about 0.98 to 1.0).

[0170] The particles 122 / 128 may have an angle of repose of from about 20° to about 45° (or from about 25° to about 35°, or from about 30° to about 40°, or from about 35° to about 45°).

[0171] The particles 122 / 128 may have a Hausner ratio of from about 1.0 to about 1.5 (or from about 1.0 to about 1.2, or from about 1.1 to about 1.3, or from about 1.2 to about 1.35, or from about 1.3 to about 1.5).

[0172] The particles 122 / 128 may have a bulk density of from about 0.3 g / cm 3 to about 0.8 g / cm 3 (or from about 0.3 g / cm 3 to about 0.6 g / cm 3 , or from about 0.4 g / cm 3 to about 0.7 g / cm 3 , or from about 0.5 g / cm 3 to about 0.6 g / cm 3 , or from about 0.5 g / cm 3 to about 0.8 g / cm 3 ).

[0173] Depending on the temperature and shear rate of processing 112 and the composition and relative concentration of components 102, 104 and 106, different shapes of structures constituting particles 122 / 128 have been observed. Typically, particles 122 / 128 include substantially spherical particles (having a roundness of about 0.97 or greater). However, other structures have been observed in particles 122 / 128, including discs and elongated structures. Therefore, particles 122 / 128 may include one or more of the following: (a) substantially spherical particles with a roundness of 0.97 or greater, (b) disc structures with an aspect ratio of about 2 to about 10, and (c) elongated structures with an aspect ratio of 10 or greater. Each of the (a), (b) and (c) structures has an emulsion stabilizer dispersed on the outer surface of the (a), (b) and (c) structures and / or embedded in the exterior of the (a), (b) and (c) structures. At least some of the (a), (b) and (c) structures may be agglomerated. For example, (c) elongated structures may be laid on the surface of (a) substantially spherical particles.

[0174] The particles 122 / 128 may have a sintering window within 10°C, preferably within 5°C, of ​​the sintering window of the thermoplastic polymer 102 (comprising one or more PP-polyamides and optionally one or more other thermoplastic polymers).

[0175] Applications of Thermoplastic Polymer Granules

[0176] The thermoplastic polymer particles described herein can be used in 3D printing processes, particularly those that use selective laser sintering to promote particle consolidation. The thermoplastic polymer particles of the present disclosure can exhibit properties superior to polymer particles having irregular shapes or wider particle distributions (such as those commercially available). In a non-limiting example, the thermoplastic polymer particles of the present disclosure can consolidate at lower laser powers and provide reduced void formation in articles prepared by 3D printing.

[0177] The 3D printing process of the present disclosure may include: depositing the thermoplastic polymer particles of the present disclosure onto a surface in a specified shape, and once deposited, heating at least a portion of the thermoplastic polymer particles to promote consolidation thereof and form a consolidated body (article), such that the consolidated body has a void percentage of about 1% or less after consolidation. For example, the heating and consolidation of the thermoplastic polymer particles may be performed in a 3D printing device using a laser, such that the heating and consolidation are performed by selective laser sintering.

[0178] Any thermoplastic polymer particles disclosed herein may be formulated in a composition suitable for 3D printing. The composition and type of the elastomeric microparticles may be selected based on various factors, such as, but not limited to, the laser power used for selective laser sintering, the type of article to be prepared, and the conditions of intended use of the article.

[0179] Examples of items that can be 3D printed using the thermoplastic polymer particles of the present disclosure include, but are not limited to, containers (e.g., for food, beverages, cosmetics, personal care compositions, pharmaceuticals, etc.), shoe soles, toys, furniture parts and decorative household items, plastic gears, screws, nuts, bolts, cable ties, automotive parts, medical supplies, prostheses, orthopedic implants, aviation / aircraft related parts, preparation of artifacts to aid learning in education, 3D anatomical models to assist surgery, robots, biomedical devices (orthotics), household appliances, dentistry, electronic devices, sporting goods, etc.

[0180] Other applications of the thermoplastic microparticles of the present disclosure may include, but are not limited to, use as fillers in paints and powder coatings, inkjet materials, and electrophotographic toners, etc. In some cases, the thermoplastic microparticles may have other preferred characteristics, such as diameter and span, that may be useful for such other applications.

[0181] Non-limiting example embodiments

[0182] The first non-limiting embodiment of the present disclosure is a composition comprising: particles comprising a thermoplastic polymer (e.g., a thermoplastic elastomer) and an emulsion stabilizer (e.g., nanoparticles and / or a surfactant) associated with the outer surface of the particles. The first non-limiting embodiment may include one or more of the following: Element 1: wherein the emulsion stabilizer comprises nanoparticles and at least some of the nanoparticles are embedded in the outer surface of the particles; Element 2: wherein the thermoplastic polymer is present at 90% to 99.5% by weight of the particles; Element 3: wherein at least some of the particles have voids, the voids comprising the emulsion stabilizer at the void / thermoplastic polymer interface; Element 4: Element 3 and wherein the emulsion stabilizer comprises nanoparticles and the nanoparticles are embedded in the void / thermoplastic polymer interface; Element 5: Element 3 and wherein the voids comprise a carrier fluid having a viscosity of 1,000 cSt to 150,000 cSt at 25°C; Element 6: wherein the particles further comprise elongated structures on the surface of the particles, wherein the elongated structures comprise the thermoplastic polymer and An emulsion stabilizer is associated with the outer surface of the elongated structure; Element 7: wherein the emulsion stabilizer forms a coating that covers less than 5% of the surface of the particle; Element 8: wherein the emulsion stabilizer forms a coating that covers at least 5% of the surface of the particle; Element 9: wherein the emulsion stabilizer forms a coating that covers at least 25% of the surface of the particle; Element 10: wherein the emulsion stabilizer forms a coating that covers at least 50% of the surface of the particle; Element 11: wherein the particle further comprises a carrier fluid having a viscosity of 1,000 cSt to 150,000 cSt at 25°C; Element 12: wherein the carrier fluid is present in about 5% by weight or less of the particle; Element 13: wherein the nanoparticles have an average diameter of 1 nm to 500 nm; Element 14: wherein the nanoparticles have an average diameter of 10 m 2 / g to 500m 2The BET surface area per g; Element 15: wherein the thermoplastic polymer is selected from: polyamide, polyurethane, polyethylene, polypropylene, polyacetal, polycarbonate, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyester (e.g., polylactic acid), polyether, polyethersulfone, polyetheretherketone, polyacrylate, polymethacrylate, polyimide, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymer, polyarylether, polyarylene sulfide, polysulfone, polyetherketone, polyamide-imide, polyetherimide, polyetherester, copolymer comprising a polyether block and a polyamide block (PEBA or polyether block amide), grafted or ungrafted thermoplastic polyolefin, functionalized or non-functionalized ethylene / vinyl monomer polymer, functionalized or non-functionalized ethylene / (meth)acrylic acid alkyl ester, functionalized or non-functionalized (meth)acrylic acid polymer, functionalized or non-functionalized ethylene / vinyl monomer / (meth)acrylic acid alkyl ester terpolymer, ethylene / vinyl monomer / carbonyl terpolymer, ethylene / (meth)acrylic acid alkyl ester / carbonyl terpolymer, methyl methacrylate-butadiene-styrene (MBS) type core-shell polymer, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymer, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resin, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymer, polyacrylonitrile, silicone and any combination thereof; Element 16: wherein the melting point or softening temperature of the thermoplastic polymer is from 50 °C to 450 °C; Element 17: wherein the particles have a D10 of about 0.5 μm to about 125 μm, a D50 of about 1 μm to about 200 μm and a D90 of about 70 μm to about 300 μm, wherein D10 < D50 < D90; Element 18: wherein the particles have a diameter span of about 0.2 to about 10; Element 19: wherein the particles have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm and a D90 of about 70 μm to about 120 μm, wherein D10 < D50 < D90; Element 20: Element 19 and wherein the particles have a diameter span of about 1.0 to about 2.5; Element 21: wherein the particles have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm and a D90 of about 110 μm to about 175 μm, wherein D10 < D50 < D90; Element 22: Element 21 and wherein the particles have about 0.6 to about 1.Diameter span of 5; Element 23: wherein the particles have a D10 of about 75 μm to about 125 μm, a D50 of about 100 μm to about 200 μm, and a D90 of about 125 μm to about 300 μm, where D10 < D50 < D90; Element 24: Element 23 and wherein the solidified particles have a diameter span of about 0.2 to about 1; Element 25: wherein the particles have a roundness of about 0.90 to about 1.0; and Element 26: wherein the particles have a Hausner ratio of about 1.0 to about 1.5. Examples of combinations include, but are not limited to, combinations of Element 1 with one or more of Elements 2-26; combinations of Element 3 (optionally in combination with Element 4 and / or Element 5) with one or more of Elements 2 and 4-26; and combinations of two or more of Elements 1-15.

[0183] A second non-limiting embodiment of the present disclosure is a method comprising: mixing a mixture comprising a thermoplastic polymer, a carrier fluid immiscible with the thermoplastic polymer (e.g., a thermoplastic elastomer), and an emulsion stabilizer (e.g., nanoparticles and / or a surfactant) at a temperature greater than the melting point or softening temperature of the thermoplastic polymer and at a shear rate high enough to disperse the thermoplastic polymer in the carrier fluid; cooling the mixture to below the melting point or softening temperature of the thermoplastic polymer to form solidified particles, the solidified particles comprising the thermoplastic polymer and the emulsion stabilizer associated with the outer surface of the solidified particles; and separating the solidified particles from the carrier fluid. The first non-limiting embodiment may include one or more of the following: element 1; element 2; element 3; element 4; element 5; element 6; element 7; element 8; element 9; element 10; element 11; element 12; element 13; element 14; element 15; element 16; element 17; element 18; element 19; element 20; element 21; element 22; element 23; element 24; element 25; element 26; element 27: wherein the thermoplastic polymer is present in the mixture at 5% to 60% by weight of the mixture; element 28: wherein the emulsion stabilizer is present in the mixture at 0.05% to 5% by weight of the thermoplastic polymer; element 29: wherein the carrier fluid is selected from the group consisting of silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, alkyl-terminated polyethylene glycol, paraffin, liquid petrolatum, vison oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, calophyllum oil oil), palm oil, parleam oil, grapeseed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, almond oil, castor oil, avocado oil, jojoba oil, olive oil, cereal germ oil, lanolic acid esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty acid esters, higher fatty acids, fatty alcohols, polysiloxanes modified with fatty acids, polysiloxanes modified with fatty alcohols, polysiloxanes modified with polyoxyalkylenes, and any combination thereof; Element 30: Element 29 and wherein the silicone oil is selected from the group consisting of polydimethylsiloxane, methylphenylpolysiloxane, alkyl-modified polydimethylsiloxane, alkyl-modified methylphenylpolysiloxane, amino-modified polydimethylsiloxane, amino-modified methylphenylpolysiloxane, fluorine-modified polydimethylsiloxane, fluorine-modified methylphenylpolysiloxane, polyether-modified polydimethylsiloxane, polyether-modified methylphenylpolysiloxane, and any combination thereof; Element 31: wherein the carrier fluid has a viscosity of 0.6 g / cm 3 Up to 1.5g / cm 3 The density of thermoplastic polymers is 0.7 g / cm 3 Up to 1.7g / cm 3Density; Element 32: wherein mixing is performed in an extruder; Element 33: wherein mixing is performed in a stirred reactor; and Element 33: wherein the mixture further comprises a surfactant. Examples of combinations include, but are not limited to, those described with respect to the first non-limiting embodiment; a combination of Element 1 with one or more of Element 27-33; a combination of Element 3 (and optionally Element 4 and / or Element 5) with one or more of Element 27-33; a combination of two or more of Element 27-33; and a combination of one or more of Element 27-33 with one or more of Element 1-26.

[0184] Terms

[0185] Clause 1. A composition comprising: a particle comprising a thermoplastic polymer (eg, a thermoplastic elastomer) and an emulsion stabilizer (eg, nanoparticles and / or a surfactant) associated with an outer surface of the particle.

[0186] Clause 2. The composition of Clause 1, wherein the emulsion stabilizer comprises nanoparticles and at least some of the nanoparticles are embedded in the outer surface of the particles.

[0187] Clause 3. The composition of Clause 1, wherein the thermoplastic polymer is present in an amount of 90% to 99.5% by weight of the particle.

[0188] Item 4. The composition of Item 1, wherein at least some of the particles have voids comprising an emulsion stabilizer at the void / thermoplastic polymer interface.

[0189] Item 5. The composition of Item 4, wherein the emulsion stabilizer comprises nanoparticles and the nanoparticles are embedded in the void / thermoplastic polymer interface.

[0190] Clause 6. The composition of Clause 4, wherein the voids comprise a carrier fluid having a viscosity of 1,000 cSt to 150,000 cSt at 25°C.

[0191] Item 7. The composition of Item 1, wherein the particle further comprises elongated structures on a surface of the particle, wherein the elongated structures comprise a thermoplastic polymer and the emulsion stabilizer is associated with an outer surface of the elongated structures.

[0192] Clause 8. The composition of Clause 1, wherein the emulsion stabilizer forms a coating that covers less than 5% of the surface of the particle.

[0193] Clause 9. The composition of Clause 1, wherein the emulsion stabilizer forms a coating that covers at least 5% of the surface of the particle.

[0194] Clause 10. The composition of Clause 1, wherein the emulsion stabilizer forms a coating that covers at least 25% of the surface of the particle.

[0195] Clause 11. The composition of Clause 1, wherein the emulsion stabilizer forms a coating that covers at least 50% of the surface of the particle.

[0196] Clause 12. The composition of Clause 1, wherein the particles further comprise a carrier fluid having a viscosity of 1,000 cSt to 150,000 cSt at 25°C.

[0197] Clause 13. The composition of Clause 12, wherein the carrier fluid is present at about 5% or less by weight of the particle.

[0198] Item 14. The composition of Item 1, wherein the nanoparticles have an average diameter of 1 nm to 500 nm.

[0199] Clause 15. The method according to clause 1, wherein the nanoparticles have a diameter of 10 m 2 / g to 500m 2 / g of BET surface area.

[0200] Item 16. The composition according to Item 1, wherein the thermoplastic polymer is selected from the group consisting of: polyamide, polyurethane, polyethylene, polypropylene, polyacetal, polycarbonate, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyester (e.g., polylactic acid), polyether, polyethersulfone, polyetheretherketone, polyacrylate, polymethacrylate, polyimide, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymer, polyarylene ether, polyarylene sulfide, polysulfone, polyetherketone, polyamide-imide, polyetherimide, polyetherester, copolymers comprising polyether blocks and polyamide blocks (PEBA or polyether block amide), grafted or non-grafted Thermoplastic polyolefins, functionalized or non-functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / alkyl (meth)acrylates, functionalized or non-functionalized (meth)acrylic polymers, functionalized or non-functionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / alkyl (meth)acrylate / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicones, and any combination thereof.

[0201] Item 17. The composition of Item 1, wherein the thermoplastic polymer has a melting point or softening temperature of 50°C to 450°C.

[0202] Clause 18. The composition of Clause 1, wherein the particles have a D10 of about 0.5 μm to about 125 μm, a D50 of about 1 μm to about 200 μm, and a D90 of about 70 μm to about 300 μm, wherein D10 <D50<D90。

[0203] Clause 19. The composition of Clause 1, wherein the particles have a diameter span of about 0.2 to about 10.

[0204] Clause 20. The composition of clause 1, wherein the particles have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm, and a D90 of about 70 μm to about 120 μm, wherein D10 <D50<D90。

[0205] Clause 21. The composition of Clause 20, wherein the particles have a diameter span of about 1.0 to about 2.5.

[0206] Clause 22. The composition of clause 1, wherein the particles have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm, and a D90 of about 110 μm to about 175 μm, wherein D10 <D50<D90。

[0207] Clause 23. The composition of Clause 22, wherein the particles have a diameter span of about 0.6 to about 1.5.

[0208] Clause 24. The composition of clause 1, wherein the particles have a D10 of about 75 μm to about 125 μm, a D50 of about 100 μm to about 200 μm, and a D90 of about 125 μm to about 300 μm, wherein D10 <D50<D90。

[0209] Clause 25. The composition of Clause 24, wherein the solidified particles have a diameter span of about 0.2 to about 1.2.

[0210] Clause 26. The composition of Clause 1, wherein the particles have a roundness of about 0.90 to about 1.0.

[0211] Clause 27. The composition of Clause 1, wherein the particles have a Hausner ratio of about 1.0 to about 1.5.

[0212] Clause 28. The composition of Clause 1, wherein the nanoparticles comprise oxide nanoparticles.

[0213] Clause 29. The composition of Clause 1, wherein the nanoparticles comprise carbon black.

[0214] Clause 30. The composition of Clause 1, wherein the nanoparticles comprise polymer nanoparticles.

[0215] Clause 31. The composition of Clause 1, wherein the thermoplastic polymer comprises a thermoplastic elastomer.

[0216] Clause 32. The composition of Clause 1, wherein the thermoplastic polymer is a thermoplastic elastomer.

[0217] Item 33. A method comprising: mixing a mixture comprising a thermoplastic polymer (e.g., a thermoplastic elastomer), a carrier fluid immiscible with the thermoplastic polymer, and an emulsion stabilizer at a temperature greater than the melting point or softening temperature of the thermoplastic polymer and at a shear rate high enough to disperse the thermoplastic polymer in a carrier fluid; cooling the mixture to below the melting point or softening temperature of the thermoplastic polymer to form solidified particles, the solidified particles comprising the thermoplastic polymer and the emulsion stabilizer associated with the outer surface of the solidified particles; and separating the solidified particles from the carrier fluid.

[0218] Clause 34. The method of Clause 33, wherein the emulsion stabilizer comprises nanoparticles, at least some of the nanoparticles being embedded in the outer surface of the solidified particles.

[0219] Clause 35. The method of Clause 33, wherein at least some of the solidified particles have voids comprising an emulsion stabilizer at the void / thermoplastic polymer interface.

[0220] Clause 36. The method of Clause 35, wherein the emulsion stabilizer comprises nanoparticles and the nanoparticles are embedded in the void / thermoplastic polymer interface.

[0221] Clause 37. The method of claim 35, wherein the void contains a carrier fluid.

[0222] Clause 38. The composition of Clause 33, wherein the solidified particles further comprise elongated structures on a surface of the solidified particles, wherein the elongated structures comprise a thermoplastic polymer and the emulsion stabilizer is associated with an outer surface of the elongated structures.

[0223] Clause 39. The composition of Clause 33, wherein the emulsion stabilizer forms a coating that covers less than 5% of the surface of the solidified particles.

[0224] Clause 40. The composition of Clause 33, wherein the emulsion stabilizer forms a coating that covers at least 5% of the surface of the solidified particles.

[0225] Clause 41. The composition of Clause 33, wherein the emulsion stabilizer forms a coating that covers at least 25% of the surface of the solidified particles.

[0226] Clause 42. The composition of Clause 33, wherein the emulsion stabilizer forms a coating that covers at least 50% of the surface of the solidified particles.

[0227] Clause 43. The method of Clause 33, wherein the thermoplastic polymer is present in the mixture at 5% to 60% by weight of the mixture.

[0228] Clause 44. The method of Clause 33, wherein the emulsion stabilizer is present in the mixture at 0.05 wt % to 5 wt % based on the weight of the thermoplastic polymer.

[0229] Clause 45. The method of Clause 33, wherein the nanoparticles have an average diameter of 1 nm to 500 nm.

[0230] Item 46. The method according to Item 33, wherein the thermoplastic polymer is selected from the group consisting of: polyamide, polyurethane, polyethylene, polypropylene, polyacetal, polycarbonate, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyester (e.g., polylactic acid), polyether, polyether sulfone, polyether ether ketone, polyacrylate, polymethacrylate, polyimide, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymer, polyarylene ether, polyarylene sulfide, polysulfone, polyether ketone, polyamide-imide, polyetherimide, polyether ester, copolymers comprising polyether blocks and polyamide blocks (PEBA or polyether block amide), grafted or non-grafted Thermoplastic polyolefins, functionalized or non-functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / alkyl (meth)acrylates, functionalized or non-functionalized (meth)acrylic polymers, functionalized or non-functionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / alkyl (meth)acrylate / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicones, and any combination thereof.

[0231] Clause 47. The method of Clause 33, wherein the thermoplastic polymer has a melting point or softening temperature of 50°C to 450°C.

[0232] Item 48. The method according to Item 33, wherein the carrier fluid is selected from: silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, alkyl-terminated polyethylene glycol, paraffin, liquid petrolatum, vison oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, calophyllum oil, palm oil, parleam oil, grape seed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, almond oil, castor oil, avocado oil, jojoba oil, olive oil, cereal germ oil, esters of lanolic acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty acid esters, higher fatty acids, fatty alcohols, polysiloxanes modified with fatty acids, polysiloxanes modified with fatty alcohols, polysiloxanes modified with polyoxyalkylenes, and any combination thereof.

[0233] Item 49. The method according to Item 48, wherein the silicone oil is selected from: polydimethylsiloxane, methylphenylpolysiloxane, alkyl-modified polydimethylsiloxane, alkyl-modified methylphenylpolysiloxane, amino-modified polydimethylsiloxane, amino-modified methylphenylpolysiloxane, fluorine-modified polydimethylsiloxane, fluorine-modified methylphenylpolysiloxane, polyether-modified polydimethylsiloxane, polyether-modified methylphenylpolysiloxane and any combination thereof.

[0234] Clause 50. The method of Clause 33, wherein the carrier fluid has a viscosity of 1,000 cSt to 150,000 cSt at 25°C.

[0235] Clause 51. The method of clause 33, wherein the carrier fluid has a viscosity of 0.6 g / cm 3 Up to 1.5g / cm 3 The density of thermoplastic polymers is 0.7 g / cm 3 Up to 1.7g / cm 3 density.

[0236] Clause 52. The method of Clause 33, wherein the mixing is performed in an extruder.

[0237] Clause 53. The process according to Clause 33, wherein the mixing is carried out in a stirred reactor.

[0238] Clause 54. The method of Clause 33, wherein the mixture further comprises a surfactant.

[0239] Clause 55. The method of Clause 33, wherein the solidified particles have a D10 of about 0.5 μm to about 125 μm, a D50 of about 1 μm to about 200 μm, and a D90 of about 70 μm to about 300 μm, wherein D10 <D50<D90。

[0240] Clause 56. The method of Clause 33, wherein the solidified particles have a diameter span of about 0.2 to about 10.

[0241] Clause 57. The method of Clause 33, wherein the solidified particles have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm, and a D90 of about 70 μm to about 120 μm, wherein D10 <D50<D90。

[0242] Clause 58. The method of Clause 57, wherein the solidified particles have a diameter span of about 1.0 to about 2.5.

[0243] Clause 59. The method of Clause 33, wherein the solidified particles have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm, and a D90 of about 110 μm to about 175 μm, wherein D10 <D50<D90。

[0244] Clause 60. The method of Clause 59, wherein the solidified particles have a diameter span of about 0.6 to about 1.5.

[0245] Clause 61. The method of Clause 33, wherein the solidified particles have a D10 of about 75 μm to about 125 μm, a D50 of about 100 μm to about 200 μm, and a D90 of about 125 μm to about 300 μm, wherein D10 <D50<D90。

[0246] Clause 62. The method of Clause 61, wherein the solidified particles have a diameter span of about 0.2 to about 1.2.

[0247] Clause 63. The method of Clause 33, wherein the solidified particles have a roundness of about 0.90 to about 1.0.

[0248] Clause 74. The method of Clause 33, wherein the solidified particles have a Hausner ratio of about 1.0 to about 1.5.

[0249] Clause 65. The method of Clause 33, wherein the nanoparticles comprise oxide nanoparticles.

[0250] Clause 66. The method of Clause 33, wherein the nanoparticles comprise carbon black.

[0251] Clause 67. The method of Clause 33, wherein the nanoparticles comprise polymer nanoparticles.

[0252] Clause 68. The method of Clause 33, wherein the thermoplastic polymer comprises a thermoplastic elastomer.

[0253] Clause 69. The method of Clause 33, wherein the thermoplastic polymer is a thermoplastic elastomer.

[0254] Unless otherwise indicated, all numbers used in this specification and the related claims expressing the number of ingredients, characteristics (such as molecular weight), process conditions, etc. should be understood as being modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the following specification and the attached claims are approximate values, which may vary depending on the desired characteristics sought to be obtained by the embodiments of the present invention. At a minimum, and without attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be interpreted in light of the number of significant digits reported and by applying customary rounding techniques.

[0255] One or more exemplary embodiments of the embodiments of the present invention disclosed herein are presented herein. For the sake of clarity, all features of physical implementation are not described or shown in this application. It should be understood that in the development of the physical implementation of the embodiments of the present invention, many specific decisions must be made to achieve the goal of the developer, such as meeting system-related constraints, business-related constraints, government-related constraints and other constraints, which vary and change over time due to implementation. Although the efforts made by the developer may be time-consuming, such efforts will be a routine task for those of ordinary skill in the art who benefit from the present disclosure.

[0256] Although compositions and methods are described herein as "comprising" various components or steps, the compositions and methods may also "consist essentially of" or "consist of" the various components and steps.

[0257] In order to facilitate a better understanding of the embodiments of the present invention, the following examples of preferred or representative embodiments are given. The following examples should in no way be construed as limiting or defining the scope of the present invention.

[0258] Example

[0259] Example 1. Preparation of polyamide 6 microparticles in a Haake small twin screw extruder with a high shear rotor. The carrier fluid was a PDMS oil having a viscosity of 30,000 cSt or 60,000 cSt at room temperature. The concentrations of the components in the final mixture in the extruder are provided in Table 1. The order in which the components were added to the extruder was (a) the carrier fluid was added to the extruder, brought to temperature, and then room temperature polymer pellets were added to the heated carrier fluid in the extruder, or (b) the polymer pellets were added to the extruder, brought to temperature, and then the room temperature carrier fluid was added to the molten polymer in the extruder. The extruder was operated at 200 rpm for 30 minutes at temperature (see Table 1). The mixture was then discharged from the extruder onto a cold surface to provide rapid quench cooling. During heating and cooling at temperature, the torque of the extruder system was measured and no significant torque was detected.

[0260] Table 1

[0261]

[0262]

[0263] Then through 90mm The resulting mixture was filtered through #1 filter paper (available from Sigma Aldrich) to separate the polyamide 6 particles from the carrier fluid. The particles were washed three times with 300 mL of ethyl acetate. The particles were then air dried overnight in an aluminum pan in a fume hood.

[0264] Then use the Malvern MASTERSIZER TM The size of the polyamide 6 particles was characterized using a 3000 and the morphology of the particles was characterized using SEM micrographs.

[0265] Table 2

[0266] sample D50(μm) Diameter span SEM micrograph 1-1 64 1.35 Figure 2 1-2 35 1.33 Figure 3 1-3 38 0.92 Figure 4 1-4 43 0.82 Figure 5 1-5 76 0.65 Figure 6 1-6 98 0.79 Figure 7 1-7 104 0.75 Figure 8 1-8 96 0.83 Fig. 9 1-9 100 0.60 Fig.10

[0267] This example shows the following general trends: (a) increasing oil viscosity decreases particle size and diameter span (e.g., compare 1-1 with 1-3 and 1-6 with 1-5), (b) increasing polymer loading increases particle size and decreases diameter span (e.g., compare 1-4 with 1-5 and 1-1 with 1-7), and (c) increasing processing temperature decreases particle size and diameter span (e.g., compare 1-8 with 1-5 and 1-1 with 1-2).

[0268] In addition, inductively coupled plasma was performed on particles that had been digested in a HNO3 / HF / H2O2 mixture using a closed container microwave or oven for digestion to determine the silica content associated with residual PDMS. The amount of silica present in the nine samples ranged from about 234 ppm to about 374 ppm. For the sample containing about 234 ppm silica, it was estimated that only about 0.62 g of PDMS was present per 1000 g of particles. Without being limited by theory, it is believed that the PDMS is primarily present on the surface of the particles.

[0269] Example 2. Preparation of polyamide 12 microparticles in a 25 mm twin screw extruder (Werner & Pfleiderer ZSK-25). The carrier fluid was PDMS oil having a viscosity of 10,000 cSt at room temperature. The concentrations of the components in the final mixture in the extruder are provided in Table 3. The polymer pellets were added to the extruder, brought to temperature, and then dispersed with The preheated carrier fluid of R812S silica nanoparticles was added to the molten polymer in the extruder. Other operating parameters are provided in Table 3. The mixture was then discharged into a container and allowed to cool to room temperature over several hours. Light scattering particle size data is also provided in Table 3.

[0270] Table 3

[0271]

[0272] * Relative to the total combined weight of PDMS oil and polyamide

[0273] **Compared to polyamide

[0274] Example 3. 1190A10 thermoplastic polyurethane (TPU) was added to a 25 mm twin screw extruder (Werner & Pfleiderer ZSK-25) and brought to temperature, and then dispersed with Preheated 10,000 cSt PDSM oil of RX50 silica nanoparticles was added to the molten polymer in the extruder. The extruder conditions and results are presented in Table 4.

[0275] Table 4

[0276]

[0277] * Relative to the total combined weight of PDMS oil and TPU

[0278] **Relative to TPU

[0279] Example 4. Polyamide 6 particles were prepared by melt emulsification using a 1L stirred reactor from Parr Instruments. 20 wt% polyamide 6 and 80 wt% 10,000 cSt PDMS oil were loaded into the reactor. The mixture was then heated to 225°C while stirring at 1000 rpm using a dual 4-blade propeller. After about 60 minutes, the mixture was discharged from the reactor onto dry ice to quench the mixture. The mixture was then filtered and washed to recover the polymer particles. The resulting polymer particles were passed through a 150 μm sieve. Approximately 40 wt% of the polyamide 6 loaded into the reactor passed through a 150 μm sieve. Fig.11 is a SEM micrograph of the sieved particles, which shows a large range of particle sizes.

[0280] Example 5. Preparation of polyamide 12 particles by melt emulsification using a 2 L glass reactor from Buchi AG. The reactor was charged with 1 wt % of 10,000 cSt PDMS oil. R812S silica nanoparticles (based on the weight of polyamide 12 in the final mixture). The mixture was heated to 200°C before adding 23 wt% polyamide 12 pellets relative to the combined weight of PDMS oil and polyamide 12. The reactor was mixed at 500 rpm for 30 minutes. The resulting mixture was discharged and cooled to ambient temperature at a rate of about 1°C to about 3°C ​​per minute. The mixture was then washed with heptane and passed through a 90 mm The mixture was filtered through #1 filter paper to recover the polymer particles. The resulting polymer particles were air dried overnight in a fume hood. The dried particles had a D50 of about 227 μm, and the dried particles that passed through a 150 μm sieve had a D50 of about 124 μm.

[0281] Example 6. Preparation of polyamide 12 particles by melt emulsification in a 1 L glass kettle reactor (Examples 6-1 to 6-44). 10,000 cSt PDMS oil, 23% polyamide 12 (available from RTP, EMX-Grivory, or Arkema) relative to the combined weight of PDMS oil and polyamide 12, and a desired amount of silica nanoparticles ( R812S or RX50) is added to a glass kettle. The order of addition is (c) PDMS oil and silica nanoparticles are mixed into a good dispersion, and then polyamide is added, or (d) PDMS oil, polyamide and silica nanoparticles are added before mixing. Then nitrogen headspace purge is started, and the mixture is heated to a desired temperature (e.g., 200°C, 210°C or 220°C) at 260rpm within 90 minutes. Once at temperature, the rotor speed is increased to the desired rpm. Samples are collected at various times. Once completed, heating and stirring are turned off, and the reactor is allowed to cool to room temperature before discharging the mixture. The resulting mixture is filtered and washed with heptane. The resulting particles are allowed to air dry overnight in a fume hood. Optionally, the dried particles are screened (scr) through a 150μm sieve. Table 5 lists the experimental details and the resulting particle characteristics.

[0282] For samples 6-45 to 6-47, polyamide 12 particles were prepared by melt emulsification using a 2 L stainless reactor from Buchi AG. The reactor was charged with 0.67 wt % of 60,000 cSt PDMS oil. R812S silica nanoparticles (by weight of polyamide 12 in the final mixture) and the reactor was sealed without N2 purging. Before adding 30 wt% polyamide 12 pellets relative to the combined weight of PDMS oil and polyamide 12, the mixture was heated to 250°C at a ramp rate of 3.68°C / min. When the reactor temperature reached 245°C, the exhaust valve was slowly opened and the reactor was purged with N2 at a flow rate of 2-3scfh. The reactor was mixed at 650rpm for 60 minutes. The resulting mixture was cooled to less than 60°C and discharged under gentle stirring at 50rpm. The process samples collected at 40min, 60min and finally room temperature were then washed with heptane and passed through 90mm The process samples were filtered through #1 filter paper to recover the polymer particles. The resulting polymer particles were air dried overnight in a fume hood. The dried particles had a D50 of about 21.3 μm, and the final dried particles that passed through a 150 μm sieve had a D50 of about 21.5 μm.

[0283] For samples 6-48 to 6-50, polyamide 12 particles were prepared by melt emulsification using a 2 L stainless reactor from Buchi AG. The reactor was charged with 0.67 wt % of 60,000 cSt PDMS oil. R812S silica nanoparticles (by weight of polyamide 12 in the final mixture) and the reactor was purged with N2 at a flow rate of 2-3 scfh. Before adding 30 wt% polyamide 12 pellets relative to the combined weight of PDMS oil and polyamide 12, the mixture was heated to 250°C at a ramp rate of 3.68°C / min. The reactor was mixed at 650rpm for 60 minutes. The resulting mixture was cooled to less than 60°C and discharged under gentle stirring at 50rpm. The process samples collected at 50min, 60min time points and room temperature were then washed with heptane and passed through 90mm #1 filter paper filters these process samples to recycle polymer particles. The final room temperature sample aggregates and the particle size is not measured. The resulting polymer particles collected at 60min are air dried overnight in a fume hood. The dried particles have a D50 of about 25.8 μm, and the dried particles passing through a 150 μm sieve have a D50 of about 26.4 μm.

[0284] For samples 6-51 to 6-53, polyamide 12 particles were prepared by melt emulsification using a 2 L stainless reactor from Buchi AG. The reactor was charged with 0.67 wt % of 60,000 cSt PDMS oil. R812S silica nanoparticles (based on the weight of polyamide 12 in the final mixture) and the reactor was purged with N2 at a flow rate of 2-3 scfh. Before adding 30 wt% polyamide 12 pellets relative to the combined weight of PDMS oil and polyamide 12, the mixture was heated to 250°C at a ramp rate of 5.68°C / min. The reactor was mixed at 650rpm for 60 minutes. The resulting mixture was cooled to less than 60°C and discharged under gentle stirring at 50rpm. The process samples collected at the 60min time point and room temperature were then washed with heptane and passed through 90mm #1 filter paper filters these process samples to recycle polymer particles. Final room temperature samples aggregate and particle size is not measured. The resulting polymer particles collected at 60min are air dried overnight in a fume hood. The dried particles have a D50 of about 33.8 μm, and the dried particles passing through a 150 μm sieve have a D50 of about 34.9 μm.

[0285] Table 5

[0286]

[0287]

[0288]

[0289] "RT" means after the mixture has been cooled to room temperature.

[0290] Blank cells indicate unmeasured values.

[0291] Fig.12 A SEM micrograph of sample 6-4 is shown. Fig.13 SEM micrographs of samples 6-10 are shown. Fig.14 SEM micrographs of samples 6-15 are shown. Fig.15 SEM micrographs of samples 6-26 are shown. Fig.16 SEM micrographs of sample 6-30 are shown. Figures 17 to 20 SEM micrographs of samples 6-31, 6-32, 6-33, and 6-34 are shown.

[0292] This example shows that reducing the concentration of silica nanoparticles in the mixture increases particle size but decreases diameter span (e.g., compare 6-17 to 6-18 with 6-28 to 6-29). In addition, increasing temperature decreases particle size but increases diameter span (e.g., compare 6-17 to 6-18, 6-20 to 6-21, and 6-24 to 6-25). It can also be seen that mixing times exceeding about 10 minutes have minimal effect on particle size and diameter span.

[0293] Example 7. SEM micrographs were taken of commercially available polyamide microparticle materials for 3D printing, see Table 6.

[0294] Table 6

[0295] sample SEM micrograph <![CDATA[ADSINT TM PA11]]> Fig.21 <![CDATA[ADSINT TM PA12L]]> Fig. 22 <![CDATA[ADSINT TM PA12]]> Fig.23 <![CDATA[SINTRATEC TM PA12]]> Fig.24

[0296] Comparison of the SEM micrographs of the commercially available samples with the SEM micrographs of samples 6-4, 6-10, 6-15, 6-26, 6-30, 6-31, 6-32, 6-33, and 6-34 of Example 4 revealed that the particles prepared by the method described herein had greater roundness and higher coverage of silica nanoparticles on the surface of the polyamide particles.

[0297] Example 8. Three sets of samples were prepared using polyamide 12 from RTP. 10,000 cSt PDMS, 23 wt% polyamide 12 relative to the combined weight of PDMS and polyamide, 1 wt% R812S silica nanoparticles and optionally surfactant (wt% relative to the weight of polyamide) are placed in a glass kettle reactor. The head space is purged with argon and the reactor is kept under positive argon pressure. These components are heated to more than 220°C in about 60 minutes under 300rpm stirring. At temperature, rpm is increased to 1250rpm. The process is stopped after 90 minutes and allowed to cool to room temperature while stirring. The resulting mixture is filtered and washed with heptane. A portion of the resulting particles is screened (scr) through a 150μm sieve. Table 7 includes the additional components of the mixture and the characteristics of the resulting particles.

[0298] Table 7

[0299]

[0300] Fig.25 and Fig.26 are the volume density particle size distribution of the screened particles and the unscreened particles, respectively.

[0301] Example 9. This example shows that the addition of surfactants and the composition of the surfactants can be another tool for tailoring particle properties.

[0302] In this embodiment, the powder flow of polyurethane particles is characterized by sieving and angle of repose measurement. The sieving yield of polyurethane particles is determined in the following manner: a certain amount of polyurethane particles is exposed to a 150 μm U.S. standard sieve (ASTM E11) and the mass fraction of the particles passing through the sieve relative to the total amount of polyurethane particles is determined. The sieve is used manually under the specific conditions of no force duration. ASTM D6393-14 "Standard Test Method for Bulk Solids Characterized by Carr Indices" is used to perform angle of repose measurement using Hosokawa Micron Powder Characterization Tester PT-R.

[0303] In this example, average particle size measurements and particle size distribution were determined by optical digital microscopy. Optical images were obtained using a Keyence VHX-2000 digital microscope and version 2.3.5.1 software for particle size analysis (system version 1.93). In some cases, the Malvern MASTERSIZER TM The D 10 , D 50 and D 90 Measurement.

[0304] For light scattering techniques, the Quality Audit Standards (QAS4002) can be used. TM Glass beads with diameters ranging from 15 μm to 150 μm were purchased from Malvern Analytical Ltd. MASTERSIZER TM The 3000Aero S Dry Powder Dispersion Module analyzes samples as dry powder dispersed in air. Particle size can be derived from a graph of bulk density versus size using the instrument software.

[0305] Comparative Example 9-1. 160g of polydimethylsiloxane (PSF-30000, Clearco) was added to a 500mL glass reactor. The reactor was set to a stirring rate of 200rpm, and the temperature was raised to 190°C under a nitrogen atmosphere. Further heated to 200°C, 40g of thermoplastic polyurethane pellets were added to the polydimethylsiloxane being stirred. The thermoplastic polyurethane was poly[4,4'-methylenebis(phenyl isocyanate)-alternating-1,4-butanediol / di(propylene glycol) / polycaprolactone] (Sigma-Aldrich) with Shore hardness A84. Once the thermoplastic polyurethane pellets were fully combined with the polydimethylsiloxane, the stirring rate was increased to 500rpm and the temperature was maintained at 200°C for 60 minutes. Afterwards, stirring was stopped and the resulting slurry was allowed to cool to room temperature. The slurry was washed twice with hexane, and thermoplastic polyurethane microparticles were obtained after vacuum filtration.

[0306] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Fig. 27 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Comparative Example 9-1 at a magnification of 150X is shown. The average particle size was about 100 μm and a wide particle size distribution was obtained.

[0307] Comparative Example 9-2. Thermoplastic polyurethane microparticles from Comparative Example 9-1 were collected after filtration but before sieving and mixed with 0.25 wt % fumed silica microparticles functionalized with hexamethyldisilazane ( The thermoplastic polyurethane microparticles were then dry-blended with the fumed silica microparticles using an SKM grinder at a blending rate of 170 rpm for 30 seconds.

[0308] The dry blended microparticles were then passed through a 150 μm sieve and characterized by optical imaging and SEM. Fig.28 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Comparative Example 9-2 is shown. Fig.29A and Fig.29B Exemplary SEM images of thermoplastic polyurethane microparticles obtained in Comparative Example 9-2 at various magnifications are shown. The average particle size is about 100 μm and a wide particle size distribution is obtained, which is similar to Comparative Example 9-1. There is no evidence that silica particles are embedded on the surface of the thermoplastic polyurethane microparticles. In addition, a uniform silica coating is not obviously formed on the polyurethane microparticles.

[0309] Example 9-1. Comparative Example 9-1 was repeated, except that before the reactor was heated to temperature and the thermoplastic polyurethane particles were added, 0.25 wt % pyrogenic silica particles ( R812S) in combination with polydimethylsiloxane.

[0310] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Fig.30 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 9-1 is shown. The average particle size is about 12±16 μm. Fig.31 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 9-1 is shown.

[0311] Example 9-2. Example 9-1 was repeated except that 1.00 wt% of the same fused silica particles were used. In addition, the slurry was washed three times with hexane instead of twice.

[0312] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Fig.32 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 9-2 is shown. The average particle size is about 34±19 μm. Fig.33 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 9-2 is shown.

[0313] Example 9-3. Example 9-1 was repeated, except that the type of pyrogenic silica particles was changed to RX 50. Additionally, the slurry was washed four times with heptane instead of twice with hexane.

[0314] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging and SEM. Fig.34 Exemplary optical microscopic images of the thermoplastic polyurethane microparticles obtained in Example 9-3 are shown. Fig.35A and Fig.35BExemplary SEM images of the thermoplastic polyurethane microparticles obtained in Example 9-3 at various magnifications are shown. The average particle size obtained by optical imaging was about 48±20 μm, and the angle of repose was 32.0°. Fig.36 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 9-3 is shown.

[0315] The particle size distribution determined by a Malvern Mastersizer particle size analyzer provided D 10 , D 50 and D 90 value, thus providing a span of 1.001.

[0316] Example 9-4. Example 9-1 was repeated, except that the type of thermoplastic polyurethane pellets was changed to that purchased from BASF. 1190A. 1190A is a polyether polyurethane elastomer with a Shore hardness of A90.

[0317] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging and SEM. Fig.37 Exemplary optical microscopic images of the thermoplastic polyurethane microparticles obtained in Example 9-4 are shown. FIG. 38A to FIG. 38D Exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Example 9-4 at various magnifications are shown. The average particle size obtained by optical imaging was about 68±29 μm, and the angle of repose was 29.9°. Fig.39 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 9-4 is shown.

[0318] The particle size distribution determined by a Malvern Mastersizer particle size analyzer provided D 10 , D 50 and D 90 value, thus providing a span of 0.889.

[0319] Example 9-5. Example 9-4 was repeated, except that the processing was carried out at half the scale of Example 9-4.

[0320] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging and SEM. Fig.40 Exemplary optical microscopic images of the thermoplastic polyurethane microparticles obtained in Example 9-5 are shown. FIG. 41A to FIG. 41CExemplary SEM images of thermoplastic polyurethane microparticles obtained in Example 9-5 at various magnifications are shown. The average particle size determined by optical imaging was approximately 61±17 μm. Fig.42 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 9-5 is shown.

[0321] MASTERSIZER by Malvern TM The particle size distribution determined by the particle size analyzer provided D values ​​of 52.6 μm, 71.7 μm, and 97.2 μm, respectively. 10 , D 50 and D 90 value, thus providing a span of 0.622.

[0322] Comparison of results. The following Tables 8A and 8B summarize the formation conditions used for Comparative Examples 9-1 and 9-2 and Examples 9-1 to 9-5 and the properties of the thermoplastic polyurethane microparticles obtained in each case. The solid loading was calculated by dividing the mass of the thermoplastic polyurethane by the combined mass of the thermoplastic polyurethane and the polydimethylsiloxane.

[0323] Table 8A

[0324]

[0325]

[0326] Table 8B

[0327]

[0328]

[0329] As shown in Tables 8A and 8B and the accompanying figures, there is a broad particle size distribution and some particle agglomeration in the absence of a fused silica emulsion stabilizer (Comparative Examples 9-1 and 9-2). Different loadings and sizes of fused silica particles provide narrower particle size distributions and variations in average particle size (Examples 9-1 to 9-3). Different thermoplastic polyurethanes also cause variations in the average particle size obtained (Examples 9-3 and 9-4). Processing scale also affects particle size distribution (Examples 9-4 and 9-5).

[0330] By comparing the SEM images, it can be concluded that there is a fairly uniform coverage of silica nanoparticles on the surface of the thermoplastic polyurethane microparticles obtained by melt emulsification (Examples 9-3 to 9-5; Fig.35A / Fig.35B , FIG. 38A to FIG. 38D as well as FIG. 41A to FIG. 41CThe thermoplastic polyurethane microparticles obtained in Example 9-5 (which have a narrower particle size distribution) have a more uniform coverage / distribution of silica nanoparticles compared to the comparable thermoplastic polyurethane microparticles prepared in Example 9-4 (which have a broader particle size distribution).

[0331] Compared to thermoplastic polyurethane microparticles prepared by melt emulsification with silica nanoparticles, dry blending of thermoplastic polyurethane microparticles with silica nanoparticles resulted in little, if any, coverage of silica nanoparticles on the thermoplastic polyurethane microparticles (Comparative Example 9-2; Fig.29A / Fig.29B ).

[0332] Another comparative example of thermoplastic polyurethane microparticles is ADSINT TPU 90A NAT from ADVANC3D, which is a 3D printing composition. ADSINT TPU 90A NAT thermoplastic polyurethane microparticles have irregular microparticle shapes, such as FIG. 43A to FIG. 43E Based on the SEM image. Fig.43B and Fig.43C SEM image of ADSINT TPU 90A particles shows a non-uniform distribution of the emulsion stabilizer on the surface. Particles with irregular shapes and rough surfaces tend to have a non-uniform distribution of the emulsion stabilizer on the surface, and agglomeration can occur in rough areas and cracks, such as Fig.43C and Fig.43D As shown in the SEM image. Fig.43E The cross-sectional SEM image of shows that the emulsion stabilizer is present in a limited area and is non-uniformly distributed around the microparticles.

[0333] Substantially spherical microparticles with smooth surfaces as prepared in Examples 9-1 to 9-5 allow the emulsion stabilizer to be incorporated in a uniform manner around the outer surface of each microparticle. Substantially uniform incorporation of the emulsion stabilizer onto the microparticles can help achieve uniform properties and consistent performance of the corresponding bulk material, such as powder flow properties and processing properties.

[0334] Example 10. Selective laser sintering (SLS) was performed using a Snow White SLS printer system (Sharebot). The thermoplastic polyurethane microparticles of Example 9-3 were deposited in 30 mm x 30 mm squares using the SLS printer system and then sintered under various laser power conditions specified in Table 9 below. The percentage of voids after sintering was calculated using digital microscope software.

[0335] Table 9

[0336]

[0337] 1Multiply the reported scan rate by 0.04 to obtain the scan rate in mm / s.

[0338] As shown, effective sintering is achieved at laser powers above 20% and up to 40% power (the highest value tested), providing a low porosity material with less than 1% voids (many times less than 0.1% voids). The observed powder formation is believed to artificially reduce the amount of voids measured. In any case, the low void percentage is a characteristic of the thermoplastic polyurethane particles being effectively fused to each other. As a representative example, Fig.44 An optical image of a printed product obtained from Item 5 of Example 10 is shown.

[0339] Example 11. In this example, the powder flow of polyurethane particles is characterized by sieving and angle of repose measurements. The sieving yield of polyurethane particles is determined by exposing a certain amount of polyurethane particles to a 150 μm U.S. Standard sieve and determining the mass fraction of particles passing through the sieve relative to the total amount of polyurethane particles. The sieve is used manually without specific conditions of force duration. The angle of repose measurements are performed using ASTM D6393-14 "Standard Test Method for Bulk Solids Characterized by Carr Indices" using a Hosokawa Micron Powder Characterization Tester PT-R.

[0340] In this example, the Malvern MASTERSIZER TM 3000Aero S particle size analyzer to measure the average particle size (D 50 )、D 10 and D 90 Measurement. Optical images were obtained using a Keyence VHX-2000 digital microscope and version 2.3.5.1 software for particle size analysis (system version 1.93). The average particle size was also obtained by processing the optical images.

[0341] Comparative Example 11-1. 160g of polydimethylsiloxane (PSF-30000, Clearco) was added to a 500mL glass reactor. The reactor was set to a stirring rate of 350rpm using an overhead stirrer, and the temperature was raised to 190°C. Further heated to 200°C, 40g of thermoplastic polyurethane pellets were added to the polydimethylsiloxane being stirred. The thermoplastic polyurethane was poly[4,4'-methylenebis(phenyl isocyanate)-alternating-1,4-butanediol / di(propylene glycol) / polycaprolactone] (Sigma-Aldrich). Once the thermoplastic polyurethane pellets were fully combined with the polydimethylsiloxane, the stirring rate was increased to 500rpm and the temperature was maintained at 200°C for 60 minutes. Afterwards, stirring was stopped and the resulting slurry was allowed to cool to room temperature. The slurry was washed four times with heptane, and thermoplastic polyurethane microparticles were obtained after vacuum filtration.

[0342] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Fig.45 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-1 at a magnification of 150X is shown. The average particle size was 97.1 μm and a broad particle size distribution (span = 1.239) was obtained. Fig.46 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-1 is shown.

[0343] Comparative Example 11-2. 320 g of polydimethylsiloxane (PSF-30000, Clearco) and 0.25 wt % fumed silica microparticles functionalized with hexamethyldisilazane (obtained from Evonik) were added to a 500 mL glass reactor. RX50, 35±10m 2 / g BET surface area and 40nm average particle size). The reactor was set to a stirring rate of 200 rpm using an overhead stirrer and the temperature was raised to 190°C. The temperature was further heated to 200°C, at which time 80g of thermoplastic polyurethane pellets were added to the stirring polydimethylsiloxane. In this case, the thermoplastic polyurethane was 1190A, which is a polyether polyurethane elastomer purchased from BASF. Once the thermoplastic polyurethane pellets are fully combined with the polydimethylsiloxane, the stirring rate is increased to 500 rpm and the temperature is maintained at 200° C. for 60 minutes. Afterwards, the stirring is stopped and the resulting slurry is allowed to cool to room temperature. The slurry is washed four times with hexane and thermoplastic polyurethane microparticles are obtained after vacuum filtration.

[0344] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Fig.47 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-2 at 150X magnification is shown. The average particle size was 95.6 μm and a broad particle size distribution was obtained (span = 0.892). The angle of repose was 29.9°. Fig.48A and Fig.48B Exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-2 at various magnifications are shown. Fig.49 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-2 is shown.

[0345] Comparative Example 11-3. Comparative Example 11-1 was repeated, except that 1.0 wt % of poly[dimethylsiloxane-co-[3-(2-(2-hydroxyethoxy)ethoxy)propylmethylsiloxane] surfactant was mixed with PDMS before heating to the processing temperature. Fig.50 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-3 at 100X magnification is shown. The average particle size was 123 μm and a broad particle size distribution (span = 0.977) was obtained. Fig.51 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-3 is shown.

[0346] Comparative Example 11-4. Comparative Example 11-1 was repeated except that 2.5 wt % SPAN 80 (sorbitan maleate nonionic surfactant) was mixed with the PDMS before heating to the processing temperature. Fig.52 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-4 at 100X magnification is shown. The average particle size was 139 μm and a broad particle size distribution (span = 0.811) was obtained. Fig.53 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-4 is shown.

[0347] Example 11-1. Comparative Example 11-1 was repeated, except that 0.25 wt % pyrogenic silica particles ( RX50) and 1.0 wt% sodium dodecyl sulfate (SDS) were mixed with PDMS. Fig.54 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 11-1 at 300X magnification is shown. The average particle size was 26.8 μm and a broad particle size distribution (span = 1.251) was obtained. Fig.55 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 11-1 is shown.

[0348] Example 11-2. Comparative Example 11-1 was repeated, except that 0.25 wt % fumed silica microparticles ( ) functionalized with hexamethyldisilazane were added before the reactor was heated to temperature and the thermoplastic polyurethane polymer was added. RX50) and 2.5 wt% docusate sodium (sodium 1,4-bis(2-ethylhexyloxy)-1,4-dioxobutane-2-sulfonate, also known as dioctyl sodium sulfosuccinate) in combination with polydimethylsiloxane.

[0349] After separation, the thermoplastic polyurethane microparticles were passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Fig.56 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 11-2 at 150X magnification is shown. The average particle size was 31.5 μm and a relatively narrow particle size distribution (span=0.859) was obtained. The angle of repose was 38.2°. Fig.57 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 11-2 is shown.

[0350] Example 11-3. Comparative Example 11-1 was repeated, except that before the reactor was heated to temperature and the thermoplastic polyurethane polymer was added, 1.0 wt % pyrogenic silica particles ( RX50) and 1.0 wt% docusate sodium in combination with polydimethylsiloxane.

[0351] After separation, the thermoplastic polyurethane microparticles were passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Fig.58 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 11-3 at 150X magnification is shown. The average particle size was 51.2 μm and a relatively narrow particle size distribution (span=0.777) was obtained. The angle of repose was 32.6°. Fig.59 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 11-3 is shown.

[0352] Example 11-4. Comparative Example 11-1 was repeated, except that before the reactor was heated to temperature and the thermoplastic polyurethane polymer was added, 0.25 wt % pyrogenic silica particles functionalized with hexamethyldisilazane ( RX50) and 5 wt% DB-45 is combined with dimethicone.

[0353] After separation, the thermoplastic polyurethane microparticles were passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Fig.60An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 11-4 at 150X magnification is shown. The average particle size was 121 μm and a relatively narrow particle size distribution (span = 0.435) was obtained. Fig.61A and Fig.61B Exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Example 11-4 at various magnifications are shown. Fig.62 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 11-4 is shown.

[0354] Example 11-5. Comparative Example 11-1 was repeated, except that before the reactor was heated to temperature and the thermoplastic polyurethane polymer was added, 1.0 wt % pyrogenic silica particles ( RX50) and 2.5 wt.% DB-45 is combined with dimethicone.

[0355] After separation, the thermoplastic polyurethane microparticles were passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Fig.63 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 11-5 at 150X magnification is shown. The average particle size was 62.9 μm and a relatively narrow particle size distribution (span = 0.619) was obtained. The angle of repose was 31.3°. Fig.64 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 11-5 is shown.

[0356] Comparison of results. The following Table 10 summarizes the formation conditions used for Comparative Examples 11-1 to 11-4 and the properties of the thermoplastic polyurethane microparticles obtained in each case. The following Table 11 summarizes the formation conditions used for Examples 11-1 to 11-5 and the properties of the thermoplastic polyurethane microparticles obtained in each case.

[0357] Table 10

[0358]

[0359] Table 11

[0360]

[0361]

[0362] The combination of silica nanoparticles and sulfonate surfactants is effective in forming elastic microparticles with a narrow particle size distribution (span <0.9), and the sieving yield of the initial unscreened product is greater than 90% (Examples 11-2 to 11-5). In contrast, the sulfate surfactant (embodiment 11-1) provides a much wider particle size distribution, although with a particle size similar to that of the product prepared with the sulfonate surfactant. The particle size of the elastic microparticles formed in the absence of silica nanoparticles is much larger, and the yield after sieving is lower (Comparative Examples 11-1, 11-3 and 11-4).

[0363] Fig.65 Exemplary particle size distribution graphs are shown for Comparative Examples 11-1 and 11-4 and Example 11-3. As shown, the use of silica particles and sulfonate surfactant (Example 11-3) provides a much smaller particle size distribution.

[0364] Example 12. Selective laser sintering (SLS) was performed using a Snow White SLS printer system (Sharebot). The thermoplastic polyurethane microparticles of Example 11-3 were deposited in 30 mm x 30 mm squares using the SLS printer system and then sintered under various laser power conditions specified in Table 12 below. The percentage of voids after sintering was calculated using digital microscope software. Little to no agglomeration was observed after sintering, which may indicate good single-layer sintering performance.

[0365] Table 12

[0366]

[0367] 1 Multiply the reported scan rate by 0.04 to obtain the scan rate in mm / s.

[0368] As shown, effective sintering is achieved at laser powers above 20% and up to 45% power (the highest value tested), providing a low porosity material with a small amount of voids, which has less than 1.5% voids at laser powers above 30%. The low void percentage is a characteristic of the thermoplastic polyurethane particles being effectively fused to each other. The powder formation in entry 6 is believed to artificially reduce the amount of voids measured.

[0369] Table 13 compares the laser sintering performance of the thermoplastic polyurethane particles of Example 11-3 with those of Comparative Example 11-2 and commercial ADSINT polyurethane particles.

[0370] Table 13

[0371]

[0372]

[0373] As shown, when the thermoplastic polyurethane particles of Example 11-3 are used, effective sintering is achieved at laser powers above 20% and up to 45% power (the highest value tested), thereby providing a low porosity material. The laser sintering performance of the thermoplastic polyurethane microparticles of Example 11-3 is much better than that of the commercial ADSINT thermoplastic polyurethane microparticles, as evaluated by the porosity obtained. The laser sintering performance of the thermoplastic polyurethane microparticles of Example 11-3 is also better than that of Comparative Example 11-2 in terms of being sinterable at lower laser powers and providing lower porosity values ​​in most cases. As a representative example, Fig.66 An optical image of the printed product obtained from entry 5 of Table 12 (40% laser power) is shown.

[0374] Example 13. To a 500 mL glass kettle reactor equipped with a heating mantle was added 140 g of PDMS (PSF-10000), 0.6 g (1.0 wt%) of AEROSIL RX50 silica nanoparticles and 60 g of HTR 6108 pellets (glycol-modified polyethylene terephthalate, available from DuPont). The reactor was set to a stirring rate of 200 RPM, and the temperature was raised to 200° C. in 30 minutes under a flowing argon purge. Once the temperature reached 200° C., the stirring rate was raised to 1000 RPM. After 60 minutes, heating and stirring were stopped, and the slurry was allowed to cool to room temperature. The slurry was then washed three times with heptane, and the microparticles were separated by vacuum filtration. After vacuum drying overnight, the microparticles were subsequently sieved through a 150 μm filter. For the prepared microparticles, the average particle size (determined via optical microscopy) was 57 μm, the span was 0.87, and the angle of repose was 29.8°.

[0375] Example 14. To a 2L Buchi reactor was added 871 g of PDMS (PSF-10000) containing 2.9 g (0.5 wt%) RX50 50g PDMS / RX50 slurry and 580g ELASTOLLAN 1190A10 polyurethane. The reactor was purged with nitrogen and stirred at 200RPM. The jacket temperature was raised to 240°C in 60 minutes. Once the reactor temperature reached 200°C, the stirring rate was raised to 500RPM and the nitrogen flow was turned off. The slurry was stirred at 240°C for 30 minutes and then discharged while hot. After cooling, the slurry was then washed twice with hexane and the particles were separated by vacuum filtration. After vacuum drying overnight, the particles were subsequently sieved through a 150μm filter. For the prepared particles, the average particle size (determined via optical microscopy) was 56μm, the span was 0.59, and the angle of repose was 32.4°.

[0376] Example 15. Preparation of polypropylene microparticles in a Haake small twin screw extruder with high shear rotors. The carrier fluid was a PDMS oil having a viscosity of 30,000 cSt or 60,000 cSt at room temperature. The concentrations of the components in the final mixture in the extruder are provided in Table 15. The order in which the components were added to the extruder was either (a) the carrier fluid was added to the extruder, brought to temperature, and then room temperature polymer pellets were added to the heated carrier fluid in the extruder, or (b) the polymer pellets were added to the extruder, brought to temperature, and then the room temperature carrier fluid was added to the molten polymer in the extruder. The polypropylene pellets were added at 30% solid loading (i.e., 18 g polypropylene in 60 g PDMS). The polypropylene used was PP D115A polypropylene homopolymer available from Baskem USA. The extruder was operated at about 200 rpm for 30 minutes at a temperature of 225° C. or 250° C. (see Table 14). The mixture was then discharged from the extruder onto a cold surface to provide rapid quench cooling. During heating and cooling at temperature, the torque of the extruder system was measured. The resulting mixture was then washed three times with 300 mL of heptane and passed through a 90 mm The resulting mixture was filtered through #1 filter paper (available from Sigma Aldrich) to separate the polypropylene particles from the carrier fluid. The particles were then allowed to air dry overnight in an aluminum pan in a fume hood. The morphology of the dried polypropylene particles was characterized using SEM micrographs and the Malvern MASTERSIZER TM The size of the dried polypropylene particles was characterized using a 3000Aero S particle size analyzer. Thermal properties were evaluated using differential scanning calorimetry (DSC) to determine melting and crystallization temperatures. Inductively coupled plasma (ICP) determined the presence of residual silicone oil on the particles.

[0377] In this embodiment, the powder flow of the microparticles is characterized by sieving and angle of repose measurement. The sieving yield of the microparticles is determined in the following manner: a certain amount of microparticles is exposed to a 250 mm American Standard Sieve (ASTM E11) and the mass fraction of the microparticles passing through the sieve relative to the total amount of the microparticles is determined. The sieve is manually used in the absence of the specific conditions of the force duration. ASTM D6393-14 "Standard Test Method for Bulk Solids Characterized by Carr Indices" is used to perform angle of repose measurement using Hosokawa Micron Powder Characterization Tester PT-R. The results are described in Table 14.

[0378] SEM micrographs depict smooth, round particles with a fairly wide size distribution. These particles were selectively laser sintered as a single layer in a Sharebot SnowWhite SLS printer. Particles made with 30,000 cSt oil required higher laser power to produce a robustly sintered single layer relative to particles made with 60,000 cSt oil. Particles made with 60,000 cSt oil exhibited extreme edge curling as laser power was increased.

[0379] Table 14

[0380]

[0381] Example 16. Polyamide 12 microparticles were prepared in a 25 mm twin screw extruder (Werner & Pfleiderer ZSK-25). The carrier fluid was PDMS oil having a viscosity of 60,000 cSt at room temperature. The concentrations of the components in the final mixture in the extruder are provided in Table 15. The polymer pellets were added to the extruder, brought to temperature, and then the preheated carrier fluid in which the silica nanoparticles were dispersed was added to the molten polymer in the extruder. Other operating parameters are provided in Table 15. The mixture was then discharged into a container and allowed to cool to room temperature over several hours. Light scattering particle size data is also provided in Table 15.

[0382] Table 15

[0383]

[0384] * Relative to the total combined weight of PDMS oil and polyamide

[0385] **Relative to the weight of polyamide

[0386] ***X24 is a silicon dioxide powder available from ShinEtsu, having an average particle size of 0.1 μm, a specific gravity of 1.8, and a water content of 2%.

[0387] Therefore, the present invention is well suited to achieve the goals and advantages mentioned and those inherent therein. The specific embodiments disclosed above are exemplary only, because the present invention can be modified and implemented in different but equivalent ways that are obvious to those skilled in the art who benefit from the teachings herein. In addition, it is expected that there is no limitation on the details of construction or design shown herein, except as described in the following claims. Therefore, it is obvious that the specific exemplary embodiments disclosed above can be changed, combined or modified, and all such changes are considered to be within the scope and essence of the present invention. The present invention disclosed exemplarily herein can be appropriately implemented in the absence of any element not specifically disclosed herein and / or any optional element disclosed herein. Although compositions and methods are described with "comprising", "containing" or "including" various components or steps, compositions and methods can also be "essentially composed of various components and steps" or "composed of various components and steps". All numbers and ranges disclosed above may change by some amount. Whenever a numerical range with a lower limit and an upper limit is disclosed, any number and any included range falling within the range are specifically disclosed. Specifically, each value range disclosed herein (in the form of "about a to about b", or equivalently, "about a to b", or equivalently, "about ab") should be understood to set forth each numerical value and range encompassed within the broader value range. In addition, the terms in the claims have their plain, ordinary meaning unless otherwise explicitly and clearly defined by the patentee. In addition, the indefinite articles "a" or "an" used in the claims are defined herein to mean that there is one or more than one of the element it introduces.

Claims

1. A method, comprising: shearing a mixture comprising the thermoplastic polymer, the carrier fluid immiscible with the thermoplastic polymer, and the emulsion stabilizer at a temperature greater than the melting point or softening temperature of the thermoplastic polymer and at a shear rate high enough to disperse the thermoplastic polymer as molten droplets in a carrier fluid in the presence of the emulsion stabilizer; cooling the mixture to below the melting point or softening temperature of the thermoplastic polymer to form solidified particles comprising the thermoplastic polymer and the emulsion stabilizer associated with an outer surface of the solidified particles; and separating the solidified particles from the carrier fluid, The emulsion stabilizer comprises a plurality of nanoparticles, and at least a portion of the nanoparticles are disposed on the outer surface of the solidified particles in the form of a coating. 2 . The method of claim 1 , wherein at least some of the nanoparticles are embedded in the outer surface of the solidified particles.

3. The method of claim 1, wherein the emulsion stabilizer comprises nanoparticles selected from the group consisting of oxide nanoparticles, carbon black, polymer nanoparticles, and any combination thereof.

4. The method of claim 1, wherein the solidified particles further comprise elongated structures on the surface of the solidified particles, wherein the elongated structures comprise the thermoplastic polymer and the emulsion stabilizer is associated with an outer surface of the elongated structures.

5. The method of claim 1, wherein the emulsion stabilizer is present in the mixture at 0.01 wt% to 10 wt% based on the weight of the thermoplastic polymer.

6. The method of claim 1, wherein the thermoplastic polymer is present in the mixture at 5% to 60% by weight of the mixture.

7. A composition comprising: A particle comprising a thermoplastic polymer and an emulsion stabilizer associated with an outer surface of the particle, wherein the particle has a roundness of 0.90 to 1.0, wherein the emulsion stabilizer comprises nanoparticles, and at least a portion of the nanoparticles are disposed on the outer surface of the particles in the form of a coating, The roundness of the particles is C EA / P, where P is the circumference of the particle, and C EA is the circumference of a circle whose area is equal to the area of ​​the actual particle, determined by optical microscopy, Wherein the particles are prepared by the method according to any one of claims 1 to 6.

8. The composition of claim 7, wherein at least some of the nanoparticles are embedded in the outer surface of the particles.

9. The composition of claim 7 wherein at least some of the particles have voids therein, the voids containing the emulsion stabilizer at the void / thermoplastic polymer interface.

10. The composition of claim 9, wherein the voids comprise a carrier fluid having a viscosity of 1,000 cSt to 150,000 cSt at 25°C.

11. The composition according to claim 10, wherein the carrier fluid is selected from the group consisting of silicone oil, polyethylene glycol, paraffin, mink oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, crabapple oil, palm oil, parleam oil, grape seed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, almond oil, castor oil, avocado oil, jojoba oil, olive oil, cereal germ oil, fatty acid esters, higher fatty acids, fatty alcohols, polysiloxanes modified with fatty acids, polysiloxanes modified with fatty alcohols, polysiloxanes modified with polyoxyalkylenes, and any combination thereof.

12. A composition according to claim 11, wherein the carrier fluid is selected from esters of lanolin acid and esters of oleic acid.

13. The composition of claim 11, wherein the carrier fluid is selected from fluorinated silicone oils.

14. The composition of claim 13, wherein the carrier fluid is selected from perfluorinated silicone oils.

15. The composition according to claim 11, wherein the carrier fluid is selected from alkyl-terminated polyethylene glycol.

16. The composition of claim 11, wherein the carrier fluid is selected from liquid petrolatum.

17. The composition of claim 11, wherein the carrier fluid is selected from esters of lauric acid and esters of stearic acid.

18. The composition according to claim 7, further comprising: elongated structures on the surface of the particle, wherein the elongated structures comprise the thermoplastic polymer and the emulsion stabilizer is associated with an outer surface of the elongated structures.

19. The composition of claim 7, wherein the emulsion stabilizer forms a coating that covers at least 25% of the surface of the particle.

20. The composition according to claim 7, wherein the thermoplastic polymer is selected from the group consisting of polyamides, polyurethanes, polyacetals, polycarbonates, polyesters, polyethers, polyacrylates, polyimides, acrylonitrile butadiene styrene, polyarylene sulfide, polysulfones, polyether ketones, polyamide-imides, copolymers comprising polyether blocks and polyamide blocks, grafted or non-grafted thermoplastic polyolefins, functionalized or non-functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / alkyl (meth)acrylates, functionalized or non-functionalized (meth)acrylic polymers. The present invention relates to a polyol, a polyol, a polyol, a polystyrene-based ...

21. The composition of claim 20, wherein the thermoplastic polymer is selected from the group consisting of polyarylethers, polymethacrylates, polyetherimides, polyetheresters, and vinyl polymers.

22. The composition of claim 20, wherein the thermoplastic polymer is selected from the group consisting of polystyrene, polyvinyl chloride, polytetrafluoroethylene, chlorinated or chlorosulfonated polyethylene, and polyvinylidene fluoride.

23. The composition of claim 20, wherein the thermoplastic polymer is selected from the group consisting of polybutylene terephthalate, polyethylene terephthalate, polyethylene naphthalate, polytrimethylene terephthalate, and polyhexylene terephthalate.

24. The composition of claim 20, wherein the thermoplastic polymer is selected from the group consisting of polyethersulfone and polyetheretherketone.

25. The composition of claim 20, wherein the thermoplastic polymer is selected from polyphenylene sulfide.

26. The composition of claim 20, wherein the thermoplastic polymer is selected from polyethylene and polypropylene.

27. The composition of claim 20, wherein the thermoplastic polymer is selected from polylactic acid.

28. The composition of claim 7, wherein the thermoplastic polymer is a first thermoplastic polymer, and wherein the particles further comprise a second thermoplastic polymer and a compatibilizer.

29. The composition of claim 7, wherein the particles have a D10 of 0.5 μm to 125 μm, a D50 of 1 μm to 200 μm, and a D90 of 70 μm to 300 μm, wherein D10 <D50<D90, Where D10, D50 and D90 refer to the diameters at which 10%, 50% and 90% of the sample, on a volume basis, consists of particles with diameters less than the stated diameter values, respectively, as determined by light scattering techniques.

30. The composition of claim 7, wherein the particles have a diameter span of 0.2 to 10, Wherein the diameter span is defined as (D90-D10) / D50, where D10, D50 and D90 refer to the diameters at which 10%, 50% and 90% of the sample, on a volume basis, consists of particles with diameters less than the stated diameter value, respectively, as determined by light scattering techniques.

31. The composition of claim 7, wherein the particles have a Hausner ratio of 1.0 to 1.5, The Hausner ratio is given by H r =ρ 振实 / ρ 堆积 Calculate, where ρ 堆积 is the bulk density according to ASTM D6393-14, and ρ 振实 It is the tap density according to ASTM D6393-14.

32. The composition of claim 7, wherein the nanoparticles comprise particles selected from the group consisting of oxide nanoparticles, carbon black, polymer nanoparticles, and any combination thereof.

Citation Information

Patent Citations

  • Producing an item by the selective fusion of polymer powder layers

    CN102232018A

  • Nylon / silica composite microsphere, preparation method and application thereof

    CN107254163A

  • Emulsion method for the manufacture of ultra-fine spherical polymer particles

    CN107257819A

  • Production method for silica-coated spherical silicone elastomer particles and silica-coated spherical silicone elastomer particles

    WO2019078028A1